Biodegradable resin composition, non-woven fabric and manufacturing method thereof

Through electrospinning technology and the specially made biodegradable resin composition, the problems of easy cutting of nonwoven fabric fibers and bead formation are solved, and high-quality, continuously manufactured biodegradable nonwoven fabrics are achieved.

CN119571544APending Publication Date: 2025-03-07AISIKA LIBIO CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411210213.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-05
Filing Date
2024-08-30
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, when using biodegradable resin to make nonwoven fabrics, it is difficult to achieve continuous manufacturing of fibers and stable quality, and problems of fiber cutting or bead formation are prone to occur.

Method used

The yarn is formed by preparing a resin solution including a biodegradable resin composition and an organic solvent, and applying a voltage to the resin solution using electrospinning technology. The resin composition includes diol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, and the resistance in the molten state is 3 MΩ to 10 MΩ.

Benefits of technology

Continuous manufacturing of biodegradable nonwoven fabrics is achieved, with fiber diameters ranging from 50 nm to 1,000 nm, and has excellent biodegradability and water resistance, avoiding the problems of fiber cutting and bead formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571544A_ABST
    Figure CN119571544A_ABST
Patent Text Reader

Abstract

The invention relates to a biodegradable resin composition, a non-woven fabric and a manufacturing method thereof. The method includes preparing a biodegradable resin solution including a biodegradable resin composition and an organic solvent, the biodegradable resin composition including a first biodegradable resin. The biodegradable resin solution is then spun by applying a voltage to the biodegradable resin solution. The first biodegradable resin includes a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to a method of making a biodegradable nonwoven fabric and the biodegradable nonwoven fabric made thereby. Background Art

[0002] Recently, with the increased concern about environmental issues, it is necessary to solve the disposal problem of various household items, especially disposable products. Specifically, petroleum-based polymer materials are cheap and have excellent processability, so they are widely used to make various products such as films, fibers, packaging materials, bottles and containers. However, products made of petroleum-based polymer materials release harmful substances when they are incinerated at the end of their service life. In addition, depending on the type of product, it takes hundreds of years for them to decompose naturally.

[0003] In order to overcome these limitations of petroleum-based polymer materials, research on biodegradable resins that decompose in a relatively short period of time is being actively conducted. Polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), and polybutylene succinate (PBS) are introduced as biodegradable resins.

[0004] Specifically, nonwoven fabrics are materials that can be used for various products, and the demand for manufacturing eco-friendly nonwoven fabrics is increasing. However, when using biodegradable resins to manufacture fibers to produce nonwoven fabrics, there is a complexity that the fibers are easily cut or formed into beads. In addition, when using biodegradable resins as raw materials, it is difficult to achieve a continuous process for manufacturing fibers, and the quality of the manufactured fibers deteriorates due to increased thickness or reduced uniformity. Summary of the invention

[0005] Embodiments of the present invention have been made in view of the above considerations, and an object of the present invention is to provide a biodegradable nonwoven fabric having excellent biodegradability and water resistance; and a method of manufacturing the biodegradable nonwoven fabric.

[0006] According to an embodiment of the present invention, the above and other objects can be achieved by providing a method for manufacturing a biodegradable nonwoven fabric, the method comprising preparing a biodegradable resin solution comprising a biodegradable resin composition and an organic solvent, the biodegradable resin composition comprising a first biodegradable resin; and spinning the biodegradable resin solution by applying a voltage to the biodegradable resin solution, wherein the first biodegradable resin comprises a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid.

[0007] In an embodiment of the present invention, in the spinning step, a voltage of 15 kV to 30 kV may be applied to the biodegradable resin solution.

[0008] In an embodiment of the present invention, in the spinning step, a release rate of the biodegradable resin solution may be 0.1 mL / min to 1.0 mL / min.

[0009] In an embodiment of the present invention, in the spinning step, a first zone for discharging the biodegradable resin solution and a second zone separated from the first zone in the gravity direction and including yarn produced from the biodegradable resin solution discharged from the first zone may be used, wherein the distance between the first zone and the second zone is 100 mm to 500 mm.

[0010] According to an embodiment of the present invention, the biodegradable resin composition may further include a second biodegradable resin, wherein the second biodegradable resin includes one or more selected from the group consisting of polybutylene succinate, polylactic acid, polybutylene adipate, polybutylene succinate adipate, polybutylene succinate terephthalate, polyhydroxybutyrate-valerate, polycaprolactone and polybutylene succinate adipate terephthalate.

[0011] In an embodiment of the present invention, the biodegradable resin composition may include an applier, wherein the applier may be included in an amount of 10 ppm to 100 ppm based on the total weight of the biodegradable resin composition.

[0012] In an embodiment of the present invention, the resistance of the biodegradable resin composition in a molten state may be 3 MΩ to 10 MΩ.

[0013] In an embodiment of the present invention, the method may further include drying the spun biodegradable resin solution after spinning the biodegradable resin solution.

[0014] According to another embodiment of the present invention, a biodegradable nonwoven fabric is provided, which includes: a first biodegradable resin including a diol, an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid; a biodegradable resin composition including the first biodegradable resin; and a yarn containing the biodegradable resin composition and having a diameter of 50nm to 1,000nm, wherein the biodegradable resin composition has a resistance of 3MΩ to 10MΩ in a molten state.

[0015] In an embodiment of the present invention, the biodegradable nonwoven fabric may include an organic solvent in an amount of 10 ppm or less based on the total weight of the yarn.

[0016] In embodiments of the invention, the yarn may include processing additives.

[0017] According to another embodiment of the present invention, there is provided a biodegradable resin composition including a biodegradable resin including a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid, wherein the biodegradable resin composition has a resistance of 3 MΩ to 10 MΩ in a molten state.

[0018] In an embodiment of the present invention, the biodegradable resin composition may include an application agent.

[0019] The biodegradable nonwoven fabric manufactured by the method of manufacturing a biodegradable nonwoven fabric according to the present invention includes a biodegradable resin, and thus it can be advantageously naturally biodegraded at the end of its life, thereby not requiring incineration or releasing harmful substances.

[0020] In the case of using the method for manufacturing biodegradable nonwoven fabric according to the present invention and the biodegradable nonwoven fabric manufactured thereby, yarn can be manufactured by electrostatic spinning, so that yarn can be continuously produced by biodegradable resin composition. Therefore, yarn with nanometer size diameter can be effectively manufactured. In addition, the biodegradable nonwoven fabric comprising the yarn is light in weight and has high surface area and porosity, so it can also be applied to products requiring moisture absorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 An apparatus for preparing a biodegradable resin composition according to an embodiment of the present invention is schematically shown.

[0022] Figure 2 An apparatus for manufacturing a biodegradable nonwoven fabric by electrospinning according to an embodiment of the present invention is schematically shown.

[0023] Figure 3 A photograph of the biodegradable nonwoven fabric produced in Example 1 is shown.

[0024] Figure 4 A photograph of the biodegradable nonwoven fabric produced in Comparative Example 1 is shown. DETAILED DESCRIPTION

[0025] The structural or functional descriptions of the embodiments disclosed in this specification are merely shown for the purpose of describing the embodiments according to the technical ideas of the present invention. The embodiments according to the technical ideas of the present invention can be implemented in various forms other than the embodiments disclosed in this specification, and should not be interpreted as the technical ideas of the present invention being limited to the embodiments described in this specification.

[0026] In this specification, when a certain component is "included", this means that only the component is included, or the component may also include other components unless there is no different disclosure. In addition, it should be understood that, unless otherwise stated, all numerical ranges representing physical property values, dimensions, etc. of components described in this specification are modified by the term "about" in all cases. In addition, in this specification or application document, "ppm" means based on weight.

[0027] Hereinafter, a method for manufacturing a biodegradable nonwoven fabric according to the present invention and a biodegradable nonwoven fabric manufactured thereby are described.

[0028] The method for manufacturing a biodegradable nonwoven fabric according to the present invention includes the steps of preparing a biodegradable resin solution including a biodegradable resin composition and an organic solvent, wherein the biodegradable resin composition includes a first biodegradable resin; and applying a voltage to the biodegradable resin solution to discharge the biodegradable resin solution, wherein the first biodegradable resin includes a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid.

[0029] The method of manufacturing a biodegradable nonwoven fabric according to the present invention includes the step of preparing a biodegradable resin solution including a biodegradable resin composition containing a first biodegradable resin and an organic solvent.

[0030] The biodegradable resin composition includes a first biodegradable resin. The first biodegradable resin includes a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid.

[0031] The first biodegradable resin can include glycol residues, aromatic dicarboxylic acid residues and aliphatic dicarboxylic acid residues. The glycol residues can be derived from glycols, the aromatic dicarboxylic acid residues can be derived from aromatic dicarboxylic acids, and the aliphatic dicarboxylic acid residues can be derived from aliphatic dicarboxylic acids. The first biodegradable resin can include glycol components, aromatic dicarboxylic acid components and aliphatic dicarboxylic acid components. The glycol components can be derived from glycols, the aromatic dicarboxylic acid components can be derived from aromatic dicarboxylic acids, and the aliphatic dicarboxylic acid components can be derived from aliphatic dicarboxylic acids.

[0032] In this specification, a diol residue may also be referred to as a diol. In this specification, a dicarboxylic acid residue may also be referred to as a dicarboxylic acid. In this specification, a residue may also be referred to as a component.

[0033] The diol may be an aliphatic diol.The diol may be a bio-derived diol. The diol may be at least one selected from the group consisting of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2,2-dimethyl-1,3-propylene glycol, 2,2-diethyl-1,3-propylene glycol, 2-ethyl-2-isobutyl-1,3-propylene glycol, 1,2-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 2-ethyl-1,3-hexanediol, 2,4-dimethyl-2-ethyl-1,3-hexanediol, 2,2,4-trimethyl-1,6-hexanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, 1,10-decanediol and 1,12-octadecanediol or a derivative thereof.

[0034] The diol may be at least one selected from the group consisting of 1,4-butanediol, 1,2-ethanediol, 1,3-propylene glycol, diethylene glycol, and neopentyl glycol, or a derivative thereof.

[0035] The diol may be at least one selected from the group consisting of 1,4-butanediol, 1,2-ethylene glycol, 1,3-propylene glycol, or a derivative thereof.

[0036] The diol may include 1,4-butanediol or a derivative thereof.

[0037] The aromatic dicarboxylic acid may be at least one selected from the group consisting of phthalic acid, terephthalic acid, isophthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 4,4′-biphenyl dicarboxylic acid, 4,4′-biphenyl ether dicarboxylic acid, anthracene dicarboxylic acid, phenanthrene dicarboxylic acid or derivatives thereof.

[0038] The aromatic dicarboxylic acid may be at least one selected from the group consisting of terephthalic acid, dimethyl terephthalate, 2,6-naphthalene dicarboxylic acid, isophthalic acid, or a derivative thereof.

[0039] The aromatic dicarboxylic acid may include terephthalic acid, dimethyl terephthalate, or a derivative thereof.

[0040] The aliphatic dicarboxylic acid may be at least one selected from the group consisting of oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, or derivatives thereof.

[0041] The aliphatic dicarboxylic acid may be at least one selected from the group consisting of adipic acid, succinic acid, and sebacic acid, or a derivative thereof.

[0042] The aliphatic dicarboxylic acid may include adipic acid or a derivative thereof.

[0043] In the first biodegradable resin, the molar ratio of all diol residues (including diols): all dicarboxylic acid residues (including aromatic dicarboxylic acids and aliphatic dicarboxylic acids) may be about 1:0.9 to about 1:1.1. The molar ratio of all diol residues: all dicarboxylic acid residues may be about 1:0.95 to about 1:1.05.

[0044] In the first biodegradable resin, the molar ratio of aromatic dicarboxylic acid residues: aliphatic dicarboxylic acid residues may be about 3:7 to about 7:3. In the first biodegradable resin, the molar ratio of aromatic dicarboxylic acid residues: aliphatic dicarboxylic acid residues may be about 3.3:6.7 to about 6.7:3.3. In the first biodegradable resin, the molar ratio of aromatic dicarboxylic acid residues: aliphatic dicarboxylic acid residues may be about 4:6 to about 6:4. In the first biodegradable resin, the molar ratio of aromatic dicarboxylic acid residues: aliphatic dicarboxylic acid residues may be about 4.2:5.8 to about 5:5.

[0045] The first biodegradable resin may include a diol residue derived from 1,4-butanediol in an amount of about 90 mol% or more based on the total diols. The first biodegradable resin may include a diol residue derived from 1,4-butanediol in an amount of about 95 mol% or more based on the total diols. The first biodegradable resin may include a diol residue derived from 1,4-butanediol in an amount of about 98 mol% or more based on the total diols.

[0046] The first biodegradable resin may include an aromatic dicarboxylic acid residue derived from terephthalic acid or dimethyl terephthalate at a content of about 30 mol % to about 70 mol % based on the total dicarboxylic acid. The first biodegradable resin may include an aromatic dicarboxylic acid residue derived from terephthalic acid or dimethyl terephthalate at a content of about 35 mol % to about 65 mol % based on the total dicarboxylic acid. The first biodegradable resin may include a dicarboxylic acid residue derived from terephthalic acid or dimethyl terephthalate at a content of about 40 mol % to about 60 mol % based on the total dicarboxylic acid. The first biodegradable resin may include an aromatic dicarboxylic acid residue derived from terephthalic acid or dimethyl terephthalate at a content of about 43 mol % to about 53 mol % based on the total dicarboxylic acid.

[0047] The first biodegradable resin may include aliphatic dicarboxylic acid residues derived from adipic acid in an amount of about 30 mol% to about 70 mol% based on the total dicarboxylic acids. The first biodegradable resin may include aliphatic dicarboxylic acid residues derived from adipic acid in an amount of about 35 mol% to about 65 mol% based on the total dicarboxylic acids. The first biodegradable resin may include aliphatic dicarboxylic acid residues derived from adipic acid in an amount of about 40 mol% to about 60 mol% based on the total dicarboxylic acids. The first biodegradable resin may include aliphatic dicarboxylic acid residues derived from adipic acid in an amount of about 47 mol% to about 57 mol% based on the total dicarboxylic acids.

[0048] The first biodegradable resin may include a first block and a second block. The first biodegradable resin may have a molecular structure in which the first block and the second block are alternately bonded.

[0049] The first block may include a diol residue and an aromatic dicarboxylic acid residue. The first block may be formed by esterification of a diol and an aromatic dicarboxylic acid. The first block may include only a diol residue and an aromatic dicarboxylic acid residue. The first block may include only repeating units formed by esterification of a diol and an aromatic dicarboxylic acid. That is, the first block may mean the sum of repeating units of a diol and an aromatic dicarboxylic acid before being combined with an aliphatic dicarboxylic acid.

[0050] The second block may include a diol residue and an aliphatic dicarboxylic acid residue. The second block may be formed by esterification of a diol and an aliphatic dicarboxylic acid. The second block may include only a diol residue and an aliphatic dicarboxylic acid residue. The second block may include only repeating units formed by esterification of a diol and an aliphatic dicarboxylic acid. That is, the second block may mean the sum of repeating units of a diol and an aliphatic dicarboxylic acid before being combined with an aromatic dicarboxylic acid.

[0051] In the first biodegradable resin, the ratio (X / Y) of the number of the first block (X) to the number of the second block (Y) may be about 0.5 to about 1.5. In the first biodegradable resin, the ratio (X / Y) of the number of the first block (X) to the number of the second block (Y) may be about 0.6 to about 1.4. In the first biodegradable resin, the ratio (X / Y) of the number of the first block (X) to the number of the second block (Y) may be about 0.7 to about 1.3. In the first biodegradable resin, the ratio (X / Y) of the number of the first block (X) to the number of the second block (Y) may be about 0.75 to about 1.2. In addition, in the first biodegradable resin, the ratio (X / Y) of the number of the first block (X) to the number of the second block (Y) may be 0.8 to 1. In the first biodegradable resin, the number of the first block may be less than the number of the second block.

[0052] The number of first blocks may be about 30 to about 300. The number of first blocks may be about 40 to about 250. The number of first blocks may be about 50 to about 220. The number of first blocks may be about 60 to about 200. The number of first blocks may be about 70 to about 200. The number of first blocks may be about 75 to about 200.

[0053] The number of the first block may vary depending on the content of the aromatic dicarboxylic acid, the molecular weight of the first biodegradable resin, and the alternation ratio to be described below. That is, the number of the first block may increase with an increase in the molar ratio of the aromatic dicarboxylic acid, an increase in the molecular weight of the first biodegradable resin, and an increase in the alternation ratio to be described below.

[0054] The number of second blocks may be about 30 to about 300. The number of second blocks may be about 40 to about 250. The number of second blocks may be about 50 to about 220. The number of second blocks may be about 60 to about 200. The number of second blocks may be about 70 to about 200. The number of second blocks may be about 75 to about 200.

[0055] The amount of the second block may depend on the following: the content of the aliphatic dicarboxylic acid, the molecular weight of the first biodegradable resin, and the degree of alternation to be described below.

[0056] When the first biodegradable resin includes the first block and the second block within the above range, the biodegradable nonwoven fabric according to the present invention can have appropriate biodegradability and appropriate mechanical strength, or in other words, have an improved balance of biodegradability and mechanical strength. In addition, when the first biodegradable resin includes the first block and the second block within the above range, the biodegradable nonwoven fabric can have improved flexibility.

[0057] When the first biodegradable resin includes the first block and the second block within the above range, the biodegradable nonwoven fabric according to the present invention can have appropriate biodegradability while having appropriate durability against UV rays, etc. The first block can be represented by the following Formula 1:

[0058] Formula 1

[0059]

[0060] In Formula 1, R1 may be a substituted or unsubstituted arylene group having 6 to 20 carbon atoms, R2 may be a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and m may be 1 to 20.

[0061] R1 may be a substituted or unsubstituted phenylene group, and R2 may be a butene group.

[0062] The second block can be represented by the following Formula 2:

[0063] Formula 2

[0064]

[0065] In Formula 2, R3 and R4 may each independently be a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and n may be 1 to 20.

[0066] R3 and R4 may be butene groups.

[0067] The first biodegradable resin may have a structure in which the first block and the second block are alternately bonded to each other. The first biodegradable resin may be represented by the following Formula 3:

[0068] Formula 3

[0069]

[0070] In Formula 3, R1 may be a substituted or unsubstituted arylene group having 6 to 20 carbon atoms, R2 may be a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and m may be 1 to 20. In addition, R3 and R4 are each independently a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and n is 1 to 20.

[0071] The diol residue may include a residue of 1,4-butanediol or a derivative thereof, the aromatic dicarboxylic acid residue may include a residue of terephthalic acid or a derivative thereof, and the aliphatic dicarboxylic acid residue may include a residue of adipic acid or a derivative thereof.

[0072] For example, the first biodegradable resin may include a first block comprising residues of 1,4-butanediol or a derivative thereof and residues of terephthalic acid or a derivative thereof.

[0073] Alternatively, the first biodegradable resin may include a first block comprising residues of 1,4-butanediol or a derivative thereof and residues of dimethyl terephthalate or a derivative thereof.

[0074] The first biodegradable resin may include a second block comprising residues of 1,4-butanediol or a derivative thereof and residues of adipic acid or a derivative thereof.

[0075] Alternatively, the first biodegradable resin may include a second block comprising residues of 1,4-butanediol or a derivative thereof and residues of succinic acid or a derivative thereof.

[0076] The first biodegradable resin according to an embodiment of the present disclosure may include a first block including residues of 1,4-butanediol or its derivatives and residues of terephthalic acid or its derivatives; and a second block including residues of 1,4-butanediol or its derivatives and residues of adipic acid or its derivatives.

[0077] The first block may be represented by the following Formula 4, and the second block may be represented by the following Formula 5:

[0078] Formula 4

[0079]

[0080] In Formula 4, m may be 1 to 20.

[0081] Formula 5

[0082]

[0083] In Formula 5, n may be 1 to 20.

[0084] The first biodegradable resin may be represented by the following Formula 6:

[0085] Formula 6

[0086]

[0087] In Formula 6, m may be 1 to 20, and n may be 1 to 20.

[0088] When the first block and the second block satisfy the configuration, it may be more advantageous to provide a biodegradable nonwoven fabric having excellent biodegradability and water degradability and improved performance.

[0089] In addition, when the first biodegradable resin includes the first block and the second block within the above range, the biodegradable nonwoven fabric according to the present invention may have appropriate mechanical properties and appropriate UV resistance.

[0090] Since the first and second blocks have the above-mentioned characteristics, the mechanical properties of the biodegradable nonwoven fabric according to the present invention can be improved.

[0091] Since the first and second blocks have the above-mentioned characteristics, the biodegradable nonwoven fabric according to the present invention can have appropriate UV resistance.

[0092] Since the first and second blocks have the above-mentioned characteristics, the biodegradable nonwoven fabric according to the present invention can have an appropriate biodegradation rate.

[0093] Since the first and second blocks have the above-mentioned characteristics, the biodegradable nonwoven fabric according to the present invention can have an appropriate biodegradation rate and improved UV resistance.

[0094] The first biodegradable resin may include the following bonding structures 1 to 3:

[0095] Bonding structure 1

[0096] Aromatic dicarboxylic acid - Diol - Aliphatic dicarboxylic acid -

[0097] Bonding structure 2

[0098] Aromatic dicarboxylic acid-diol-aromatic dicarboxylic acid-

[0099] Bonding structure 3

[0100] Aliphatic dicarboxylic acid-diol-aliphatic dicarboxylic acid-

[0101] The diol included in the bonding structure 1 is located between and bonded to the aromatic dicarboxylic acid and the aliphatic dicarboxylic acid. The diol included in the bonding structure 1 may be located between and bonded to the aromatic dicarboxylic acid and the aliphatic dicarboxylic acid and may be directly ester-bonded to the aromatic dicarboxylic acid and the aliphatic dicarboxylic acid.

[0102] In addition, the diol included in the bonding structure 2 is located between two aromatic dicarboxylic acids (also referred to as first and second aromatic dicarboxylic acids) and is bonded to the two aromatic dicarboxylic acids. The diol included in the bonding structure 2 may be located between the two aromatic dicarboxylic acids and directly ester-bonded to the two aromatic dicarboxylic acids.

[0103] Furthermore, the diol included in the bonding structure 3 is located between the two aliphatic dicarboxylic acids and is bonded to both of the aliphatic dicarboxylic acids. The diol included in the bonding structure 3 may be located between the two aliphatic dicarboxylic acids and be directly ester-bonded to the two aliphatic dicarboxylic acids.

[0104] In the first biodegradable resin, the bonding structure 1 may be represented by the following Formula 7:

[0105] Formula 7

[0106]

[0107] In Formula 7, R1 is a substituted or unsubstituted arylene group having 6 to 20 carbon atoms, R2 is a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and R3 is a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms.

[0108] In the first biodegradable resin, the bonding structure 2 may be represented by the following Formula 8:

[0109] Formula 8

[0110]

[0111] In Formula 8, R1 is a substituted or unsubstituted arylene group having 6 to 20 carbon atoms, and R2 is a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms.

[0112] In the first biodegradable resin, the bonding structure 3 may be represented by the following Formula 9:

[0113] Formula 9

[0114]

[0115] In Formula 9, R2 is a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, and R3 is a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms.

[0116] In addition, the bonding structure 1 can be represented by the following formula 10:

[0117] Formula 10

[0118]

[0119] In addition, the bonding structure 2 can be expressed by the following formula 11.

[0120] Formula 11

[0121]

[0122] In addition, the bonding structure 3 can be represented by the following formula 12:

[0123] Formula 12

[0124]

[0125] The first biodegradable resin may have alternating ratios.

[0126] The alternation ratio refers to the ratio of the diol bonded between the aromatic dicarboxylic acid and the aliphatic dicarboxylic acid in the diol. That is, the alternation ratio may be the ratio of the diol included in the bonding structure 1 in the diol. The alternation ratio may be obtained by dividing the number of moles of the diol included in the bonding structure 1 by the sum of the number of moles of the diol included in the bonding structure 1, the number of moles of the diol included in the bonding structure 2, and the number of moles of the diol included in the bonding structure 3.

[0127] That is, the alternating ratio may be a ratio of diols bonded between heterogeneous dicarboxylic acids in the total diols.

[0128] The alternation ratio can be calculated according to the following equation 1:

[0129] Equation 1:

[0130]

[0131] In Equation 1, DM1 is a molar ratio of the diol included in the bonding structure 1 , DM2 is a molar ratio of the diol included in the bonding structure 2 , and DM3 is a molar ratio of the diol included in the bonding structure 3 .

[0132] In the first biodegradable resin, the alternating ratio may be about 0.3 to about 0.7. In the first biodegradable resin, the alternating ratio may be about 0.37 to about 0.59. In the first biodegradable resin, the alternating ratio may be about 0.4 to about 0.56. In the first biodegradable resin, the alternating ratio may be about 0.45 to about 0.53.

[0133] Furthermore, the first biodegradable resin includes a hard segment ratio.

[0134] The hard segment ratio refers to the ratio of the diol bonded between the aromatic dicarboxylic acid and the aromatic dicarboxylic acid in the diol.

[0135] The hard segment ratio may be a molar ratio of the diol included in the bonding structure 2 in the total diol. The hard segment ratio may be obtained by dividing the number of moles of the diol included in the bonding structure 2 by the sum of the number of moles of the diol included in the bonding structure 1, the number of moles of the diol included in the bonding structure 2, and the number of moles of the diol included in the bonding structure 3.

[0136] The hard segment ratio can be expressed by the following equation 2:

[0137] Equation 2:

[0138]

[0139] In Equation 2, DM1 is the molar ratio of the diol included in the bonding structure 1 , DM2 is the molar ratio of the diol included in the bonding structure 2 , and DM3 is the molar ratio of the diol included in the bonding structure 3 .

[0140] The hard segment ratio may be about 0.15 to about 0.35. The hard segment ratio may be about 0.2 to about 0.3. The hard segment ratio may be about 0.21 to about 0.29. The hard segment ratio may be about 0.22 to about 0.28.

[0141] Furthermore, the first biodegradable resin includes a soft segment.

[0142] The soft segment ratio refers to the ratio of diol bonded between aliphatic dicarboxylic acid and aliphatic dicarboxylic acid in diol.

[0143] The soft segment ratio may be a molar ratio of the diol included in the bonding structure 3 in the total diol. The soft segment ratio may be obtained by dividing the number of moles of the diol included in the bonding structure 3 by the sum of the number of moles of the diol included in the bonding structure 1, the number of moles of the diol included in the bonding structure 2, and the number of moles of the diol included in the bonding structure 3.

[0144] The soft segment ratio can be expressed by the following equation 3:

[0145] Equation 3

[0146]

[0147] In Equation 3, DM1 is the molar ratio of the diol included in the bonding structure 1 , DM2 is the molar ratio of the diol included in the bonding structure 2 , and DM3 is the molar ratio of the diol included in the bonding structure 3 .

[0148] The soft segment ratio may be about 0.16 to about 0.36. The soft segment ratio may be about 0.21 to about 0.31. The soft segment ratio may be about 0.22 to about 0.30. The hard segment ratio may be about 0.23 to about 0.29.

[0149] The soft segment ratio may be greater than the hard segment ratio.

[0150] The ratio of the hard segment to the soft segment may be about 0.92 to about 0.99. That is, DM2 divided by DM3 may be about 0.92 to about 0.99.

[0151] The alternating ratio, hard segment ratio, and soft segment ratio can be measured by nuclear magnetic resonance spectroscopy. The first biodegradable resin can be dissolved in a solvent such as CDCl3, and can be measured at room temperature using a nuclear magnetic resonance (NMR) instrument. 1 H-NMR and / or 13 C-NMR analysis was performed.

[0152] When the diol is 1,4-butanediol, the aromatic dicarboxylic acid is terephthalic acid or dimethyl terephthalate, and the aliphatic dicarboxylic acid is adipic acid, analysis of the first biodegradable resin by nuclear magnetic resonance spectroscopy may include a first peak, a second peak, a third peak, a fourth peak, a fifth peak, a sixth peak, a seventh peak, an eighth peak, a ninth peak, a tenth peak, and an eleventh peak.

[0153] For example, when the diol is 1,4-butanediol, the aromatic dicarboxylic acid is terephthalic acid or dimethyl terephthalate, and the aliphatic dicarboxylic acid is adipic acid, analysis of the first biodegradable resin by nuclear magnetic resonance spectroscopy may include a peak derived from the diol of bonding structure 1, a peak derived from the diol of bonding structure 2, and a peak derived from the diol of bonding structure 3 at about 3.5 ppm to about 4.6 ppm.

[0154] In the range of about 3.5ppm to about 4.6ppm, the first peak, the second peak, the third peak and the fourth peak can be defined in the order from high ppm to low ppm. In addition, in the range of about -3.4ppm to about -4.3ppm based on the ppm of the ninth peak, the first peak, the second peak, the third peak and the fourth peak can be defined in the order from high ppm to low ppm. Here, the first peak can be derived from the glycol included in the second bonding unit, the second peak and the third peak can be derived from the glycol included in the first bonding unit, and the fourth peak can be derived from the glycol included in the third bonding unit.

[0155] The -ppm direction may be a high field direction or a shielding direction. For example, -3.4ppm may mean a position of 3.4ppm in the high field direction. For example, -3.4ppm may mean a position of 3.4ppm in the shielding direction.

[0156] Furthermore, analysis of the first biodegradable resin by nuclear magnetic resonance spectroscopy may include a peak derived from diol of bonding structure 1, a peak derived from diol of bonding structure 2, and a peak derived from diol of bonding structure 3 also at about 1.0 ppm to about 2.5 ppm.

[0157] In the range of about 1.0ppm to about 2.5ppm, the tenth peak, the fifth peak, the sixth peak, the seventh peak, the eighth peak and the eleventh peak can be defined in the order from high ppm to low ppm. In the range of about -6.0ppm to about -6.7ppm based on the ppm of the ninth peak, the fifth peak, the sixth peak, the seventh peak, the eighth peak and the eleventh peak can be defined in the order from high ppm to low ppm. Here, the fifth peak can be derived from the glycol included in the second bonding unit, the sixth peak and the seventh peak can be derived from the glycol included in the first bonding unit, and the eighth peak can be derived from the glycol included in the third bonding unit.

[0158] In addition, within the range of about 7.5ppm to about 8.5ppm, a ninth peak may be formed. The ninth peak may be derived from an aromatic dicarboxylic acid. The ninth peak may be derived from an aromatic ring included in an aromatic dicarboxylic acid. The ninth peak may be derived from an aromatic ring included in terephthalic acid or dimethyl terephthalate.

[0159] The tenth peak and the eleventh peak may be derived from aliphatic dicarboxylic acid. The tenth peak and the eleventh peak may be derived from adipic acid.

[0160] The first peak may be located at about -3.6ppm to about -3.68ppm based on the ppm of the ninth peak. The second peak may be located at about -3.69ppm to about -3.75ppm based on the ppm of the ninth peak. The third peak may be located at about -3.9ppm to about -3.97ppm based on the ppm of the ninth peak. The fourth peak may be located at about -3.98ppm to about -4.1ppm based on the ppm of the ninth peak. The fifth peak may be located at about -6.0ppm to about -6.19ppm based on the ppm of the ninth peak. The sixth peak may be located at about -6.2ppm to about -6.26ppm based on the ppm of the ninth peak. The seventh peak may be located at about -6.27ppm to about -6.34ppm based on the ppm of the ninth peak. The eighth peak may be located at about -6.35ppm to about -6.42ppm based on the ppm of the ninth peak. The tenth peak may be located at about -5.6ppm to about -5.8ppm based on the ppm of the ninth peak. The eleventh peak may be located at about -6.421 ppm to about -6.5 ppm based on ppm of the ninth peak. The position of the ninth peak based on ppm may be the position of each peak when the position of the ninth peak is 0 ppm.

[0161] In addition, the areas of the first peak, the second peak, the third peak, the fourth peak, the fifth peak, the sixth peak, the seventh peak, the eighth peak, the tenth peak and the eleventh peak can be normalized based on the area of ​​the ninth peak. That is, when the area of ​​the ninth peak is 1, the areas of the first peak, the second peak, the third peak, the fourth peak, the fifth peak, the sixth peak, the seventh peak, the eighth peak, the tenth peak and the eleventh peak can be relatively determined.

[0162] The alternation ratio can be obtained by the following equation 4 or 5:

[0163] Equation 4:

[0164]

[0165] In Equation 4, PA1 is the area of ​​the first peak, PA2 is the area of ​​the second peak, PA3 is the area of ​​the third peak, and PA4 is the area of ​​the fourth peak.

[0166] Equation 5:

[0167]

[0168] In Equation 5, PA5 is the area of ​​the fifth peak, PA6 is the area of ​​the sixth peak, PA7 is the area of ​​the seventh peak, and PA8 is the area of ​​the eighth peak.

[0169] The hard segment ratio can be obtained by the following equation 6 or 7:

[0170] Equation 6:

[0171]

[0172] In Equation 6, PA1 is the area of ​​the first peak, PA2 is the area of ​​the second peak, PA3 is the area of ​​the third peak, and PA4 is the area of ​​the fourth peak.

[0173] Equation 7:

[0174]

[0175] In Equation 7, PA5 is the area of ​​the fifth peak, PA6 is the area of ​​the sixth peak, PA7 is the area of ​​the seventh peak, and PA8 is the area of ​​the eighth peak.

[0176] The soft segment ratio can be obtained by the following equation 8 or 9:

[0177] Equation 8:

[0178]

[0179] In Equation 8, PA1 is the area of ​​the first peak, PA2 is the area of ​​the second peak, PA3 is the area of ​​the third peak, and PA4 is the area of ​​the fourth peak.

[0180] Equation 9

[0181]

[0182] In Equation 9, PA5 is the area of ​​the fifth peak, PA6 is the area of ​​the sixth peak, PA7 is the area of ​​the seventh peak, and PA8 is the area of ​​the eighth peak.

[0183] The area of ​​the first peak may be about 0.35 to about 0.6. The area of ​​the first peak may be about 0.4 to about 0.55. The area of ​​the first peak may be about 0.43 to about 0.5. The area of ​​the first peak may be about 0.43 to about 0.52. The area of ​​the first peak may be about 0.45 to about 0.49.

[0184] The area of ​​the second peak may be about 0.37 to about 0.57. The area of ​​the second peak may be about 0.41 to about 0.54. The area of ​​the second peak may be about 0.45 to about 0.53. The area of ​​the second peak may be about 0.45 to about 0.55. The area of ​​the second peak may be about 0.47 to about 0.53.

[0185] The area of ​​the third peak may be about 0.37 to about 0.57. The area of ​​the third peak may be about 0.41 to about 0.54. The area of ​​the third peak may be about 0.45 to about 0.53. The area of ​​the third peak may be about 0.45 to about 0.55. The area of ​​the third peak may be about 0.47 to about 0.53.

[0186] The area of ​​the fourth peak may be about 0.4 to 0.7. The area of ​​the fourth peak may be about 0.45 to about 0.65.

[0187] The area of ​​the fourth peak may be about 0.48 to about 0.6. The area of ​​the fourth peak may be about 0.48 to 0.60.

[0188] The area of ​​the fourth peak may be about 0.50 to about 0.58.

[0189] The area of ​​the fifth peak may be about 0.35 to about 0.6. The area of ​​the fifth peak may be about 0.4 to about 0.55. The area of ​​the fifth peak may be about 0.43 to about 0.53. The area of ​​the fifth peak may be about 0.43 to about 0.52. The area of ​​the fifth peak may be about 0.45 to about 0.49.

[0190] The area of ​​the sixth peak may be about 0.35 to about 0.6. The area of ​​the sixth peak may be about 0.4 to about 0.55. The area of ​​the sixth peak may be about 0.43 to about 0.5. The area of ​​the sixth peak may be about 0.45 to about 0.55. The area of ​​the sixth peak may be about 0.47 to about 0.53.

[0191] The area of ​​the seventh peak may be about 0.41 to about 0.71. The area of ​​the seventh peak may be about 0.45 to about 0.65. The area of ​​the seventh peak may be about 0.48 to about 0.6. The area of ​​the seventh peak may be about 0.45 to about 0.55. The area of ​​the seventh peak may be about 0.47 to about 0.53.

[0192] The area of ​​the eighth peak may be about 0.4 to about 0.7. The area of ​​the eighth peak may be about 0.45 to about 0.65. The area of ​​the eighth peak may be about 0.48 to about 0.6. The area of ​​the eighth peak may be about 0.48 to 0.60. The area of ​​the eighth peak may be about 0.50 to about 0.58.

[0193] The area of ​​the tenth peak may be about 0.7 to about 2.5. The area of ​​the tenth peak may be about 0.75 to about 2.

[0194] The area of ​​the tenth peak may be from 0.8 to about 1.5. The area of ​​the tenth peak may be from about 1.0 to about 1.15.

[0195] The area of ​​the tenth peak may be about 1.02 to about 1.13.

[0196] The area of ​​the eleventh peak may be about 0.7 to about 3.5. The area of ​​the eleventh peak may be about 0.7 to about 3. The area of ​​the eleventh peak may be about 0.8 to about 2.5. The area of ​​the eleventh peak may be about 1.0 to about 1.15. The area of ​​the eleventh peak may be about 1.02 to about 1.13.

[0197] In addition, the sum of the area of ​​the first peak, the area of ​​the second peak, the area of ​​the third peak, and the area of ​​the fourth peak may be about 1.49 to about 2.44. The sum of the area of ​​the first peak, the area of ​​the second peak, the area of ​​the third peak, and the area of ​​the fourth peak may be about 1.81 to about 2.16. The sum of the area of ​​the first peak, the area of ​​the second peak, the area of ​​the third peak, and the area of ​​the fourth peak may be about 1.9 to about 2.2. The sum of the area of ​​the first peak, the area of ​​the second peak, the area of ​​the third peak, and the area of ​​the fourth peak may be about 1.95 to about 2.1. Here, the sum of the area of ​​the first peak, the area of ​​the second peak, the area of ​​the third peak, and the area of ​​the fourth peak may mean the sum of the total number of ester bonds based on the number of terephthalic acid.

[0198] The sum of the area of ​​the second peak and the area of ​​the third peak may be about 0.95 to about 1.10. The sum of the area of ​​the second peak and the area of ​​the third peak may be about 0.98 to about 1.07. Here, the sum of the area of ​​the first peak and the area of ​​the third peak may mean the extension degree of the molecular bond of the first biodegradable resin.

[0199] The ratio of the area of ​​the fourth peak to the area of ​​the first peak (area of ​​the fourth peak / area of ​​the first peak) may be about 1.1 to about 1.3. The ratio of the area of ​​the fourth peak to the area of ​​the first peak may be about 0.67 to about 2.00. The ratio of the area of ​​the fourth peak to the area of ​​the first peak may be about 0.96 to about 1.40. The ratio of the area of ​​the fourth peak to the area of ​​the first peak may be about 1.15 to about 1.25. The ratio of the area of ​​the fourth peak to the area of ​​the first peak may mean the ratio of the soft segment to the hard segment in the molecular structure of the first biodegradable resin. That is, the first biodegradable resin becomes softer as the ratio of the area of ​​the fourth peak to the area of ​​the first peak increases.

[0200] The ratio of the area of ​​the fourth peak to the area of ​​the third peak (area of ​​the fourth peak / area of ​​the third peak) may be about 0.7 to about 1.89. The ratio of the area of ​​the fourth peak to the area of ​​the third peak may be about 0.91 to about 1.33. The ratio of the area of ​​the fourth peak to the area of ​​the third peak may be about 1.0 to about 1.2. The ratio of the area of ​​the fourth peak to the area of ​​the third peak may be about 1.01 to about 1.1.

[0201] The ratio of the area of ​​the first peak to the area of ​​the second peak (area of ​​the first peak / area of ​​the second peak) may be about 0.61 to about 1.62. The ratio of the area of ​​the first peak to the area of ​​the second peak may be about 0.81 to about 1.11. The ratio of the area of ​​the first peak to the area of ​​the second peak may be about 0.85 to about 0.95. The ratio of the area of ​​the first peak to the area of ​​the second peak may be about 0.86 to about 0.94.

[0202] In addition, the ratio of the area of ​​the fifth peak to the area of ​​the first peak (area of ​​the fifth peak / area of ​​the first peak) may be about 0.61 to about 1.71. The ratio of the area of ​​the fifth peak to the area of ​​the first peak may be about 0.96 to about 1.40. The ratio of the area of ​​the fifth peak to the area of ​​the first peak may be about 0.8 to about 1.2. The ratio of the area of ​​the fifth peak to the area of ​​the first peak may be about 0.9 to about 1.1.

[0203] In addition, the ratio of the area of ​​the sixth peak to the area of ​​the second peak (the area of ​​the sixth peak / the area of ​​the second peak) may be about 0.58 to about 1.71. The ratio of the area of ​​the sixth peak to the area of ​​the first peak may be about 0.86 to about 1.16. The ratio of the area of ​​the sixth peak to the area of ​​the first peak may be about 0.8 to about 1.2. The ratio of the area of ​​the sixth peak to the area of ​​the first peak may be about 0.9 to about 1.1.

[0204] In addition, the ratio of the area of ​​the seventh peak to the area of ​​the third peak (area of ​​the seventh peak / area of ​​the third peak) may be about 0.72 to about 1.92. The ratio of the area of ​​the seventh peak to the area of ​​the third peak may be about 0.91 to about 1.33. The ratio of the area of ​​the seventh peak to the area of ​​the third peak may be about 0.8 to about 1.2. The ratio of the area of ​​the seventh peak to the area of ​​the third peak may be about 0.9 to about 1.1.

[0205] In addition, the ratio of the area of ​​the eighth peak to the area of ​​the fourth peak (area of ​​the eighth peak / area of ​​the fourth peak) may be about 0.59 to about 1.75. The ratio of the area of ​​the eighth peak to the area of ​​the fourth peak may be about 0.80 to about 1.25. The ratio of the area of ​​the eighth peak to the area of ​​the fourth peak may be about 0.8 to about 1.2. The ratio of the area of ​​the eighth peak to the area of ​​the fourth peak may be about 0.9 to about 1.1.

[0206] Since the first biodegradable resin has the molecular structure as described above, the biodegradable nonwoven fabric according to the present invention may have excellent biodegradability and water degradability as well as improved physical properties.

[0207] In addition, since the first biodegradable resin has the molecular structure as described above, the biodegradable nonwoven fabric according to the present invention can have appropriate mechanical properties.

[0208] Since the first biodegradable resin has the molecular structure as described above, the biodegradable nonwoven fabric according to the present invention may have improved mechanical properties.

[0209] Since the first biodegradable resin has the molecular structure as described above, the biodegradable nonwoven fabric according to the present invention can have appropriate UV resistance.

[0210] Since the first and second blocks have the above-mentioned characteristics, the biodegradable nonwoven fabric according to the present invention can have an appropriate biodegradation rate.

[0211] The first biodegradable resin may further include a branching agent. The branching agent may include at least one selected from the group consisting of trivalent or higher alcohols, anhydrides, and trivalent or higher carboxylic acids. The branching agent may react with diols, aromatic dicarboxylic acids, and aliphatic dicarboxylic acids. Therefore, the branching agent may be included as part of the molecular structure of the first biodegradable resin.

[0212] The trivalent or higher alcohol may be at least one selected from the group consisting of glycerin, pentaerythritol, or trimethylolpropane.

[0213] The trivalent or higher hydroxycarboxylic acid may be at least one selected from the group consisting of methanetricarboxylic acid, ethanetricarboxylic acid, citric acid, benzene-1,3,5-tricarboxylic acid, 5-sulfo-1,2,4-benzenetricarboxylic acid, ethane-1,1,2,2-tetracarboxylic acid, propane-1,1,2,3-tetracarboxylic acid, butane-1,2,3,4-tetracarboxylic acid, cyclopentane-1,2,3,4-tetracarboxylic acid, and benzene-1,2,4,5-tetracarboxylic acid.

[0214] The acid anhydride may include at least one selected from the group consisting of trimellitic anhydride, succinic anhydride, methylsuccinic anhydride, ethylsuccinic anhydride, 2,3-butanedicarboxylic anhydride, 2,4-pentanedicarboxylic anhydride, 3,5-heptanedicarboxylic anhydride, 1,2,3,4-butanetetracarboxylic anhydride, maleic anhydride, dodecylsuccinic anhydride, and pyromellitic anhydride.

[0215] The content of the branching agent included in the first biodegradable resin may be about 0.1% by weight to about 5% by weight, based on the total amount of the first biodegradable resin. The content of the branching agent included in the first biodegradable resin may be about 0.1% by weight to about 3% by weight, based on the total amount of the first biodegradable resin. The content of the branching agent included in the first biodegradable resin may be about 0.1% by weight to about 1% by weight, based on the total amount of the first biodegradable resin.

[0216] Since the first biodegradable resin includes the branching agent within the range, the biodegradable nonwoven fabric according to the present invention may have appropriate mechanical characteristics and appropriate biodegradability.

[0217] The first biodegradable resin may further include polycarbonate diol. The polycarbonate diol may be bonded to the first biodegradable resin as a molecular structure to be incorporated therein.

[0218] The polycarbonate diol can be prepared by a dehydration condensation reaction of a carbonate and a polyol. The carbonate can be at least one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dibutyl carbonate, diphenyl carbonate and ethylene carbonate. The polyol can be at least one selected from the group consisting of ethylene glycol, diethylene glycol, neopentyl glycol, 1,6-hexanediol and 1,2-propylene glycol.

[0219] The weight average molecular weight of the polycarbonate diol may be about 500 g / mol to about 5,000 g / mol. The weight average molecular weight of the polycarbonate diol may be about 700 g / mol to about 4,000 g / mol. The weight average molecular weight of the polycarbonate diol may be about 800 to about 3,500 g / mol.

[0220] In addition, the viscosity of the polycarbonate diol may be about 300 cps to about 20,000 cps. The viscosity of the polycarbonate diol may be about 400 cps to about 15,000 cps. The viscosity of the polycarbonate diol may be about 500 cps to about 14,000 cps.

[0221] The OH value of the polycarbonate diol may be about 20 mgKOH / g to about 350 mgKOH / g. The OH value of the polycarbonate diol may be about 30 mgKOH / g to about 300 mgKOH / g.

[0222] The polycarbonate diol may be included in the first biodegradable resin in an amount of about 0.1 parts by weight to about 5 parts by weight, based on 100 parts by weight of the first biodegradable resin. The polycarbonate diol may be included in the first biodegradable resin in an amount of about 0.5 parts by weight to about 3 parts by weight, based on 100 parts by weight of the first biodegradable resin. The polycarbonate diol may be included in the first biodegradable resin in an amount of about 1 part by weight to about 3 parts by weight, based on 100 parts by weight of the first biodegradable resin.

[0223] Since the polycarbonate diol has the above characteristics, the biodegradable nonwoven fabric according to the present invention can have appropriate wet hardness, appropriate mechanical properties, appropriate solvent resistance, and appropriate biodegradability.

[0224] The first biodegradable resin may further include polyether polyol. The polyether polyol may be bonded to the first biodegradable resin as a molecular structure to be incorporated therein.

[0225] The polyether polyol can be prepared by additionally reacting an initiator having two or more active hydrogens (-OH or NH2) with propylene oxide (PO) or ethylene oxide (EO). Examples of the polyether polyol include polypropylene glycol, polyethylene glycol, polytetramethylene ether glycol, and the like.

[0226] The weight average molecular weight of the polyether polyol may be about 500 g / mol to about 5,000 g / mol. The weight average molecular weight of the polyether polyol may be about 700 g / mol to about 4,000 g / mol. The weight average molecular weight of the polyether polyol may be about 800 g / mol to about 3,500 g / mol.

[0227] In addition, the viscosity of the polyether polyol may be about 300 cps to about 20,000 cps. The viscosity of the polyether polyol may be about 400 cps to about 15,000 cps. The viscosity of the polyether polyol may be about 500 cps to about 14,000 cps.

[0228] The polyether polyol may be included in the first biodegradable resin in an amount of about 0.1 parts by weight to about 5 parts by weight, based on 100 parts by weight of the first biodegradable resin. The polyether polyol may be included in the first biodegradable resin in an amount of about 0.5 parts by weight to about 3 parts by weight, based on 100 parts by weight of the first biodegradable resin. The polyether polyol may be included in the first biodegradable resin in an amount of about 1 part by weight to about 3 parts by weight, based on 100 parts by weight of the first biodegradable resin.

[0229] Since the polyether polyol has the above characteristics, the biodegradable nonwoven fabric according to the present invention can have appropriate wet hardness, appropriate mechanical properties, appropriate solvent resistance, and appropriate biodegradability.

[0230] The biodegradable resin composition may further include a second biodegradable resin.

[0231] The second biodegradable resin may include one or more selected from the group consisting of polybutylene succinate, polylactic acid, polybutylene adipate, polybutylene succinate-adipate, polybutylene succinate terephthalate, polyhydroxybutyrate-valerate, polycaprolactone, and polybutylene succinate adipate terephthalate.

[0232] The second biodegradable resin may include polylactic acid.

[0233] The polylactic acid may be a high melting point polylactic acid having a stereocomplex crystal. In addition, the polylactic acid may be formed by solution mixing or melt mixing of poly-L-lactic acid and poly-D-lactic acid.

[0234] The polylactic acid may include a unit represented by the following Formula 13:

[0235] Formula 13

[0236]

[0237] The polylactic acid may be a polymer including L-lactic acid units and / or D-lactic acid units. The polylactic acid may include poly-L-lactic acid and / or poly-D-lactic acid.

[0238] Poly-L-lactic acid can be a polymer mainly comprising L-lactic acid units.Poly-L-lactic acid can include L-lactic acid units in an amount of about 90mol% to about 100mol%, about 95mol% to about 100mol% or about 97mol% to about 100mol%.Poly-L-lactic acid can include units other than D-lactic acid units and / or lactic acid.Poly-L-lactic acid can include units other than D-lactic acid units and / or lactic acid in an amount of about 0mol% to about 10mol%, about 0mol% to about 5mol% or about 0mol% to about 3mol%.

[0239] Poly D-lactic acid can be a polymer mainly comprising D-lactic acid units. Poly D-lactic acid can include the D-lactic acid units of the amount of about 90 mol % to about 100 mol %, about 95 mol % to about 100 mol % or about 97 mol % to about 100 mol %. Poly D-lactic acid can include units other than L-lactic acid units and / or lactic acid. Poly D-lactic acid can include units other than L-lactic acid units and / or lactic acid of the amount of about 0 mol % to about 10 mol %, about 0 mol % to about 5 mol % or about 0 mol % to about 3 mol %.

[0240] Units other than lactic acid may include units derived from dicarboxylic acids, polyols, hydroxycarboxylic acids and lactones having functional groups capable of forming two or more ester bonds, and units derived from various polyesters, various polyethers and various polycarbonates composed of these various components.

[0241] For example, the dicarboxylic acid may include succinic acid, adipic acid, azophosphoric acid, sebacic acid, terephthalic acid, isophthalic acid, etc. The polyol may include aliphatic polyols such as ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, octanediol, glycerol, sorbitan, neopentyl glycol, diethylene glycol, triethylene glycol, polyethylene glycol, and polypropylene glycol, and aromatic polyols obtained by adding ethylene oxide to bisphenol, etc.

[0242] Hydroxycarboxylic acids may include glycolic acid, hydroxybutyric acid, etc. For example, lactones may include glycolide, ε-caprolactone glycolide, ε-caprolactone, β-propiolactone, δ-butyrolactone, β- or γ-butyrolactone, pivalolactone, δ-valerolactone, and the like.

[0243] Polylactic acid is available from Biomer Corporation under the name BIOMER TM L9000 is commercially available. In addition, polylactic acid can be obtained from Natureworks LLC or Mitsui Chemical (LACEA TM ) are commercially available. In addition, the polylactic acid may be as described in U.S. Patent Nos. 4,797,468; 5,470,944; 5,770,682; 5,821,327; 5,880,254 and 6,326,458, which are incorporated herein by reference in their entirety for all purposes.

[0244] The melting point of polylactic acid may be about 100° C. to about 240° C. The melting point of polylactic acid may be about 120° C. to about 220° C. The melting point of polylactic acid may be about 140° C. to about 200° C. The melting point of polylactic acid may be about 140° C. to about 180° C.

[0245] The crystallization temperature (Tc) of the polylactic acid may be about 50° C. to about 80° C. The crystallization temperature (Tc) of the polylactic acid may be about 55° C. to about 75° C.

[0246] The glass transition temperature (Tg) of polylactic acid may be about 20° C. to about 80° C. The glass transition temperature (Tg) of polylactic acid may be about 30° C. to about 70° C. The glass transition temperature (Tg) of polylactic acid may be about 40° C. to about 65° C. The melting point and glass transition temperature may be measured by differential scanning calorimetry (DSC) according to ASTM D-3417.

[0247] When the polylactic acid has a melting point and a glass transition temperature within the above ranges, extrusion can be facilitated. In addition, when the polylactic acid has a melting point and a glass transition temperature within the above ranges, the biodegradable nonwoven fabric according to the present invention can have improved mechanical properties.

[0248] The average molecular weight (Mn) of the polylactic acid may be about 20,000 g / mol to about 160,000 g / mol. The average molecular weight (Mn) of the polylactic acid may be about 30,000 g / mol to about 140,000 g / mol. The average molecular weight (Mn) of the polylactic acid may be about 40,000 g / mol to about 120,000 g / mol.

[0249] The weight average molecular weight (Mw) of the polylactic acid may be about 40,000 g / mol to about 200,000 g / mol. The weight average molecular weight of the polylactic acid may be about 50,000 g / mol to about 180,000 g / mol. The weight average molecular weight of the polylactic acid may be about 70,000 g / mol to about 160,000 g / mol.

[0250] The polydispersity index (Mw / Mn) of polylactic acid can be from about 1.0 to about 3.0. The polydispersity index of polylactic acid can be from about 1.1 to about 2.0. The polydispersity index of polylactic acid can be from about 1.2 to about 1.8. The weight average molecular weight and number average molecular weight can be measured by methods known to those skilled in the art. For example, the weight average molecular weight and number average molecular weight can be measured by gel permeation chromatography (GPC). The weight average molecular weight and number average molecular weight can be measured by standard monodisperse polystyrene.

[0251] Since the polylactic acid has a molecular weight and a polydispersity index within the above range, extrusion can be facilitated. In addition, since the polylactic acid has a molecular weight and a polydispersity index within the above range, the biodegradable nonwoven fabric according to the present invention can have improved mechanical properties.

[0252] The apparent viscosity of the polylactic acid measured at about 190°C and a shear rate of 1,000 / s may be about 50 Pa·s to about 600 Pa·s. The apparent viscosity of the polylactic acid measured at about 190°C and a shear rate of 1,000 / s may be about 100 Pa·s to about 500 Pa·s. The apparent viscosity of the polylactic acid measured at about 190°C and a shear rate of 1,000 / s may be about 200 Pa·s to about 400 Pa·s.

[0253] The melt index of the polylactic acid at about 190°C may be about 3 g / 10 minutes to about 15 g / 10 minutes. The melt index of the polylactic acid at about 190°C may be about 4 g / 10 minutes to about 10 g / 10 minutes. The melt index of the polylactic acid at about 190°C may be about 6 g / 10 minutes to about 10 g / 10 minutes.

[0254] The melt index of the polylactic acid at about 220°C may be about 10 g / 10 minutes to about 30 g / 10 minutes. The melt index of the polylactic acid at about 220°C may be about 12 g / 10 minutes to about 25 g / 10 minutes. The melt index of the polylactic acid at about 220°C may be about 15 g / 10 minutes to about 25 g / 10 minutes.

[0255] The melt index of the polylactic acid at about 250°C may be about 30 g / 10 minutes to about 60 g / 10 minutes. The melt index of the polylactic acid at about 250°C may be about 35 g / 10 minutes to about 55 g / 10 minutes. The melt index of the polylactic acid at about 250°C may be about 40 g / 10 minutes to about 55 g / 10 minutes.

[0256] Since the polylactic acid has a viscosity and a melt index within the above range, extrusion can be facilitated. In addition, since the polylactic acid has a viscosity and a melt index within the above range, the biodegradable nonwoven fabric according to the present invention can have improved mechanical properties.

[0257] Preferably, the biodegradable resin composition may include the above-mentioned polylactic acid (PLA)-based resin and polybutylene adipate terephthalate (PBAT)-based resin. In addition, the biodegradable resin composition may further include an inorganic filler and an additive.

[0258] The inorganic filler can be at least one selected from the group consisting of calcium sulfate, barium sulfate, talc, talc powder, bentonite, kaolin, chalk powder, calcium carbonate, graphite, gypsum, conductive carbon black, calcium chloride, iron oxide, aluminum oxide, potassium oxide, dolomite, silicon dioxide, wollastonite, titanium dioxide, silicate, mica, glass fiber, mineral fiber, etc.

[0259] In the particle size distribution of the inorganic filler obtained by the laser diffraction method, the cumulative D50 It may be about 100 μm or less, about 85 μm or less, about 70 μm or less, about 50 μm or less, about 25 μm or less, about 10 μm or less, about 5 μm or less, about 3 μm or less, or about 1 μm or less.

[0260] In addition, the specific surface area of ​​the inorganic filler can be about 100 m 2 / g or more. For example, the specific surface area of ​​the inorganic filler can be about 100m 2 / g or greater, about 105m 2 / g or greater or about 110m 2 / g or greater.

[0261] The inorganic filler may be included in the biodegradable resin composition in an amount of less than about 10 parts by weight, less than about 8 parts by weight, or less than about 6 parts by weight, based on 100 parts by weight of the biodegradable resin.

[0262] Preferably, the inorganic filler may include titanium dioxide (TiO2). When the biodegradable resin composition is spun, titanium dioxide can reduce the bonding force between the particles of the spun biodegradable resin composition, thereby forming a uniform nano-sized fiber phase and inhibiting the bead formation of the biodegradable nonwoven fabric.

[0263] As titanium dioxide, at least one of fully matte (FD) TiO2 and semi-matte (SD) TiO2 may be used. Strongly bright TiO2 is preferably not used. The FD TiO2 may be included in an amount of 3,000 ppm or more, 5,000 ppm or more, 10,000 ppm or more, 20,000 ppm or more, or 5,000 ppm to 30,000 ppm based on the total weight of the biodegradable resin composition.

[0264] The SD TiO2 may be included in an amount of 3,000 ppm or more, 3,500 ppm or more, 4,000 ppm or more, 5,000 ppm or more, or 3,000 ppm to 6,000 ppm, based on the total weight of the biodegradable resin composition.

[0265] The additives may include elongation improving agents.

[0266] As the elongation improving agent, oil such as paraffin oil, naphthenic oil or aromatic oil, or adipic acid ester such as dibutyl adipate, diethylhexyl adipate, dioctyl adipate or diisopropyl adipate can be used.

[0267] Based on the total weight of the biodegradable resin composition, the elongation improver is included in an amount of about 10 ppm to about 10,000 ppm. Based on the total weight of the biodegradable resin composition, the elongation improver is included in an amount of about 100 ppm to about 10,000 ppm. When this range is met, the mechanical properties of the biodegradable molded article can be improved.

[0268] Additives may include metal salts.

[0269] Based on the gross weight of the biodegradable resin composition, the content of the included metal salt can be from about 0.1ppm to about 1,000ppm. Based on the gross weight of the biodegradable resin composition, the content of the included metal salt can be from about 1ppm to about 500ppm. Based on the gross weight of the biodegradable resin composition, the content of the included metal salt can be from about 1ppm to about 100ppm. Based on the gross weight of the biodegradable resin composition, the content of the included metal salt can be from about 1ppm to about 50ppm. When this range is met, the biodegradation rate of the biodegradable nonwoven fabric can be appropriately controlled.

[0270] The metal salt may be at least one selected from the group consisting of nitrates, sulfates, hydrochlorides, carboxylates, etc. The metal salt may be at least one selected from the group consisting of sodium salts, calcium salts, potassium salts, magnesium salts, copper salts, iron salts, aluminum salts, silver salts, etc. The metal salt may be at least one selected from the group consisting of magnesium acetate, calcium acetate, potassium acetate, copper nitrate, silver nitrate, sodium nitrate, etc.

[0271] Additives may include chain extenders.

[0272] The chain extender may include an isocyanate. The chain extender may be at least one selected from the group consisting of a monofunctional isocyanate and a polyfunctional isocyanate. The chain extender may be at least one selected from the group consisting of toluene 2,4-diisocyanate, toluene 2,6-diisocyanate, diphenylmethane 4,4'-diisocyanate and 2,4'-diisocyanate, naphthalene 1,5-diisocyanate, xylylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate and methylene bis (4-isocyanocyclohexane). The chain extender may include a triisocyanate. The chain extender may include tris (4-isocyanatophenyl) methane.

[0273] The chain extender may be chemically bonded to the biodegradable resin. The chain extender may be chemically bonded to the polymer contained in the biodegradable resin. The chain extender may be bonded to the end of the polymer contained in the biodegradable resin. In addition, the chain extender may be bonded to the ends of three polymers contained in the biodegradable resin.

[0274] The content of the chain extender included in the biodegradable resin composition may be about 0.1% by weight to about 10% by weight, based on the total amount of the composition. The content of the chain extender included in the biodegradable resin composition may be about 1% by weight to about 8% by weight, based on the total amount of the composition. The content of the chain extender included in the biodegradable resin composition may be about 2% by weight to about 7% by weight, based on the total amount of the composition. When this range is met, the biodegradable nonwoven fabric may have suitable biodegradability.

[0275] The chain extender may react with a terminal carboxyl group or an unreacted carboxyl group contained in the biodegradable resin composition. Therefore, the biodegradable resin composition may have a low acid value.

[0276] In addition, the chain extender can couple the polymer contained in the biodegradable resin, thereby increasing the ratio of the high molecular weight polymer contained in the biodegradable resin composition. Therefore, the mechanical properties of the biodegradable nonwoven fabric can be improved.

[0277] The additive may include a heat stabilizer. The heat stabilizer may be an antioxidant having an antioxidant function. The heat stabilizer may be a phosphorus heat stabilizer. The heat stabilizer may be an antioxidant having an antioxidant function. The heat stabilizer may be a phosphorus-based heat stabilizer. The heat stabilizer may be at least one selected from the group consisting of: an amine-based high temperature heat stabilizer such as tetraethylenepentamine, triethyl phosphoacetate, phosphoric acid, phosphorous acid, polyphosphoric acid, trimethyl phosphate (TMP), triethyl phosphate, trimethyl phosphine, triphenylphosphine, etc.

[0278] Based on the total weight of glycol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, the content of heat stabilizer can be 3,000ppm or less. In particular, based on the total weight of glycol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, the content of heat stabilizer can be 10ppm to 3,000ppm, 20ppm to 2,000ppm, 20ppm to 1,500ppm or 20ppm to 1,000ppm. When the content of heat stabilizer meets the range, the polymer degradation caused by high temperature during the reaction process can be controlled, so the terminal groups of the polymer can be reduced and the color can be improved.

[0279] Additives may include UV stabilizers.

[0280] The UV stabilizer may be a hindered amine based UV stabilizer. The UV stabilizer may include SUNOVIN 904 manufactured by SUNSHOW. The UV stabilizer may have a high molecular weight. The weight average molecular weight of the UV stabilizer may be from about 1,800 g / mol to about 5,000 g / mol. The weight average molecular weight of the UV stabilizer may be from about 2,000 g / mol to about 4,000 g / mol.

[0281] The melting point of the UV stabilizer may be about 100° C. to about 200° C. The melting point of the UV stabilizer may be about 110° C. to about 150° C.

[0282] The volatilization amount of the UV stabilizer may be about 1 wt % or less when thermogravimetric analysis is performed up to about 424° C. In addition, the carbonization amount of the UV stabilizer may be about 0.1 wt % or less when thermogravimetric analysis is performed up to about 424° C.

[0283] The biodegradable resin composition according to the embodiment may include a UV stabilizer in an amount of about 0.01 to about 5 parts by weight based on about 100 parts by weight of the biodegradable resin. The biodegradable resin composition according to the embodiment may include a UV stabilizer in an amount of about 0.05 to about 1 parts by weight based on about 100 parts by weight of the biodegradable resin. The biodegradable resin composition according to the embodiment may include a UV stabilizer in an amount of about 0.1 to about 0.5 parts by weight based on about 100 parts by weight of the biodegradable resin.

[0284] Since the UV stabilizer has the above-mentioned characteristics, it may be uniformly dispersed in the biodegradable resin composition according to the embodiment.

[0285] Since the UV stabilizer has the above characteristics, the mechanical properties of the biodegradable resin composition according to the embodiment may be improved.

[0286] Since the UV stabilizer has the above-mentioned characteristics, the biodegradable resin composition according to the embodiment may have appropriate UV resistance.

[0287] Since the UV stabilizer has the above characteristics, the biodegradable resin composition according to the embodiment may have an appropriate biodegradation rate.

[0288] The biodegradable resin composition may include an application agent. The application agent may be an electrostatic application agent. The application agent may improve the conductivity of the biodegradable resin solution containing the biodegradable resin composition, and may inhibit the formation of beads in the biodegradable nonwoven fabric produced by the biodegradable resin solution. In addition, since the biodegradable resin composition includes an application agent, the nonwoven fabric may be produced by the biodegradable resin composition by an electrostatic spinning manufacturing method.

[0289] The type of the application agent is not particularly limited. In an embodiment, the application agent may be at least one of potassium acetate (CH3COOK) and magnesium acetate (Mg(CH3COO)).

[0290] Based on the gross weight of biodegradable resin composition, the content of the application agent can be 1ppm to 500ppm, 1ppm to 400ppm, 5ppm to 400ppm, 5ppm to 300ppm, 7ppm to 300ppm, 7ppm to 200ppm, 7ppm to 150ppm, 9ppm to 150ppm, 10ppm to 150ppm or 10ppm to 100ppm. When meeting the above range, the yarn with nanometer size diameter can be produced by biodegradable resin solution by electrostatic spinning manufacturing method. In addition, using electrostatic spinning manufacturing process, yarn can be continuously manufactured even at low applied voltage.

[0291] The biodegradable resin composition may include a reinforcing material.

[0292] Reinforcement material can improve the mechanical properties of biodegradable resin composition and the biodegradable nonwoven fabric made therefrom. In addition, reinforcement material can control the deformation characteristics of biodegradable nonwoven fabric due to ultraviolet rays. In addition, reinforcement material can control the biodegradability of biodegradable nonwoven fabric.

[0293] The reinforcement material may be a fiber derived from biomass. The reinforcement material may be a fiber made from organic material. The reinforcement material may be nanocellulose.

[0294] The nanocellulose may be one or more selected from the group consisting of nanocrystalline cellulose, cellulose nanofibers, microfibrillated cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, cellulose acetate, methyl cellulose, ethyl cellulose, propyl cellulose, butyl cellulose, pentyl cellulose, hexyl cellulose and cyclohexyl cellulose.

[0295] Nanocellulose can include ionically bonded metals. Nanocrystalline cellulose can include elemental sodium, sodium carboxylate salts, etc. In addition, nanocrystalline cellulose can include sulfates. Nanocrystalline cellulose can include sodium cellulose bisulfate.

[0296] Nanocellulose can be represented by the following formula 14:

[0297] Formula 14

[0298] [(C6O5H 10 ) x SO3Na] y

[0299] Where x is from 15 to 35 and y is from 1 to 10.

[0300] The specific surface area of ​​nanocellulose can be about 200 m 2 / g to about 600m 2 / g. The specific surface area of ​​nanocellulose can be about 300m 2 / g to about 500m 2 / g.

[0301] The weight average molecular weight of nanocellulose may be about 10,000 g / mol to about 40,000 g / mol. The weight average molecular weight of nanocrystalline cellulose may be about 11,000 g / mol to about 35,000 g / mol.

[0302] The moisture content of the nanocrystalline cellulose may be about 2% by weight to about 8% by weight.The moisture content of the nanocrystalline cellulose may be about 4% by weight to about 6% by weight.

[0303] The average diameter of the nanocellulose may be from about 0.5 nm to about 10 nm. The average diameter of the nanocellulose may be from about 1 nm to about 8 nm. The average diameter of the nanocellulose may be from about 1.5 nm to about 7 nm.

[0304] The average length of nanocellulose can be from about 20nm to about 200nm. The average length of nanocellulose can be from about 30nm to about 180nm. The average length of nanocellulose can be from about 35nm to about 150nm. When the diameter and length of nanocellulose meet this scope, the performance of biodegradable resin composition and the biodegradable nonwoven fabric obtained using this composition can be further improved.

[0305] The diameter and length of nanocellulose can be measured by atomic force microscopy when dispersed in water.

[0306] The content of sulfate in the nanocellulose may be about 0.6% by weight to about 1.2% by weight based on the whole nanocrystalline cellulose.The content of sulfate in the nanocrystalline cellulose may be about 0.75% by weight to about 1.1% by weight based on the whole nanocellulose.

[0307] The pH of the nanocellulose may be between 5 and 7. The pH of the nanocellulose may be between 6 and 7.

[0308] The zeta potential of nanocellulose may be about -25 mV to about -50 mV. The zeta potential of nanocellulose may be about -30 mV to about -45 mV.

[0309] Based on 100 parts by weight of the biodegradable resin composition, the content of the included nano-cellulose can be from about 0.1 parts by weight to about 2 parts by weight.Based on 100 parts by weight of the biodegradable resin composition, the content of the included nano-cellulose can be from about 0.3 parts by weight to about 1.5 parts by weight.Based on 100 parts by weight of the biodegradable resin composition, the content of the included nano-cellulose can be from about 0.5 parts by weight to about 1.2 parts by weight.Based on 100 parts by weight of the biodegradable resin composition, the content of the included nano-cellulose can be from about 0.6 parts by weight to about 1 part by weight.

[0310] Since nanocellulose has the above characteristics, it can be uniformly dispersed in the biodegradable resin composition.

[0311] Due to the above characteristics of nanocellulose, the mechanical properties of the biodegradable nonwoven fabric made from the biodegradable resin composition can be improved.

[0312] Since nanocellulose has the above characteristics, the biodegradable nonwoven fabric made from the biodegradable resin composition can have appropriate UV resistance.

[0313] Since nanocellulose has the above characteristics, the biodegradable nonwoven fabric made of the biodegradable resin composition can have an appropriate biodegradation rate.

[0314] The biodegradable resin composition may include an oligomer.

[0315] The average molecular weight of the oligomer may be from about 400 g / mol to about 1,300 g / mol. Based on the gross weight of the biodegradable resin composition, the content of the oligomer included may be from about 3,000 ppm to about 30,000 ppm. Based on the gross weight of the biodegradable resin composition, the content of the oligomer included may be from about 5,000 ppm to about 20,000 ppm. Based on the gross weight of the biodegradable resin composition, the content of the oligomer included may be from about 5,000 ppm to about 15,000 ppm. Based on the gross weight of the biodegradable resin composition, the content of the oligomer included may be from about 7,000 ppm to about 15,000 ppm.

[0316] The oligomer may be a reaction product of at least two or more of a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid. The oligomer may be a reaction product of 1,4-butanediol, terephthalic acid, and adipic acid.

[0317] The oligomer may include an oligomer in which the molar ratio of the aliphatic dicarboxylic acid is greater than the molar ratio of the aromatic dicarboxylic acid. Among the oligomers, the ratio of the oligomer including a relatively large amount of the aliphatic dicarboxylic acid may be higher than the ratio of the oligomer including a relatively large amount of the aromatic dicarboxylic acid.

[0318] Furthermore, the oligomer may appropriately control the biodegradability of the biodegradable resin composition.The oligomer may be a biodegradation regulator for appropriately controlling the biodegradability of the biodegradable resin composition.

[0319] The biodegradable resin composition may include a plasticizer.

[0320] Plasticizer can give processability or flexibility for biodegradable nonwoven fabric to be manufactured.Plasticizer can be glycerine, acrylate, glycerine, glyceryl monostearate (GMS), sorbitol or its mixture.Based on the gross weight of biodegradable resin combination, the content of plasticizer can be less than 2.0% by weight, 1.8% by weight or less, 1.6% by weight or less, 1.4% by weight or less, 1.2% by weight or less or 1.0% by weight or less.When meeting this scope, the biodegradable nonwoven fabric made of biodegradable resin combination can be given flexibility, and can keep a certain degree of water resistance during the normal use period of the user.

[0321] The biodegradable resin composition may include a heterogeneous biodegradable resin in addition to the first biodegradable resin and the second biodegradable resin.

[0322] The heterogeneous biodegradable resin may be at least one selected from the group consisting of polybutylene azelaic terephthalate (PBAzT), polyhydroxybutyrate (PHB), polybutylene succinate (PBS), polybutylene sebacate terephthalate (PBSeT), polybutylene succinate terephthalate (PBST) and polyhydroxyalkanoate (PHA).

[0323] Based on the biodegradable resin of 100 weight portions, the content of the heterogeneous biodegradable resin included can be about 10 weight portions to about 100 weight portions.Based on the biodegradable resin of 100 weight portions, the content of the heterogeneous biodegradable resin included can be about 10 weight portions to about 60 weight portions.Based on the biodegradable resin of 100 weight portions, the content of the heterogeneous biodegradable resin included can be about 20 weight portions to about 50 weight portions.When satisfying this scope, the mechanics, optics and chemical properties of biodegradable resin can be supplemented, so that the biodegradable nonwoven fabric made of biodegradable resin composition can have suitable UV resistance and suitable biodegradation rate.

[0324] The quantity of the carboxyl terminal groups of biodegradable resin composition can be about 50eq / ton or less. For example, the quantity of the carboxyl terminal groups of biodegradable resin composition can be about 50eq / ton or less, about 48eq / ton or less, about 45eq / ton or less or about 42eq / ton or less. By regulating the quantity of the carboxyl terminal groups within the scope, when biodegradable resin composition is extruded and forms a biodegradable nonwoven fabric, deterioration can be prevented and improved mechanical properties can be achieved.

[0325] The intrinsic viscosity (IV) of biodegradable resin composition can be about 0.9dl / g or more. The intrinsic viscosity of biodegradable resin composition can be about 0.95dl / g or more, about 1.0dl / g or more, about 1.1dl / g or more, about 1.2dl / g or more or about 1.3dl / g or more. The intrinsic viscosity of biodegradable resin composition can be about 0.95dl / g to about 1.7dl / g. The intrinsic viscosity of biodegradable resin composition can be about 1.3dl / g to about 1.7dl / g. The intrinsic viscosity of biodegradable resin composition can be about 1.4dl / g to about 1.7dl / g. When regulating the intrinsic viscosity within the range, biodegradable resin composition can be injected smoothly, thereby improving the manufacturing process efficiency of biodegradable nonwoven fabric.

[0326] The maximum load of the biodegradable resin composition may be 2 kgf to 5 kgf, 2.5 kgf to 5 kgf, 3 kgf to 5 kgf, or 4 kgf to 4.8 kgf.

[0327] The biodegradable resin composition may have a yield strength of 0.5 MPa to 8 MPa, 0.5 MPa to 7 MPa, 1 MPa to 7 MPa, 1.2 MPa to 7 MPa, or 1.2 MPa to 5.4 MPa.

[0328] The elongation of the biodegradable resin composition may be 300% to 700%, 350% to 700%, 400% to 700%, 450% to 700%, or 500% to 700%.

[0329] The maximum load, yield strength and elongation of biodegradable resin composition can be the index of the cohesiveness of biodegradable resin composition.The maximum load, yield strength and elongation of biodegradable resin composition can change according to the content range of titanium dioxide included in the biodegradable resin composition.When satisfying this scope, the cohesive force between the particles of the biodegradable resin composition through spinning can reduce, thereby can form the fiber phase of uniform nanometer size, and can suppress the bead formation of biodegradable nonwoven fabric.

[0330] The maximum load, yield strength and elongation of the biodegradable resin composition can be measured according to the following methods.

[0331] After overlapping two samples made of the biodegradable resin composition and having a thickness of 300 μm, a load of about 3.7 kg was applied thereto, and they were bonded by pressing at 130° C. for 30 minutes, followed by measurement at a tensile speed of 100 mm / min.

[0332] The electrical resistance of the biodegradable resin composition in a molten state can be measured.

[0333] In order to measure the resistance, the biodegradable resin composition is melted at about 240° C. under a nitrogen atmosphere, and then a bubble removal process is performed, and a platinum electrode can be inserted into the molten biodegradable resin composition. Next, the measurement can be performed at about 50V for about 120 seconds under a molten state condition. Specifically, the resistance in the molten state can be calculated according to the following equation 10:

[0334] Equation 10:

[0335] Resistance in molten state (MΩ) = A / L × V / I

[0336] In Equation 10, A is the area of ​​the electrode (cm 2 ), L is the distance between the electrodes (cm), I is the applied current (amperes), and V is the applied voltage (V).

[0337] The resistance of the biodegradable resin composition in the molten state can be 1MΩ to 15MΩ, 1MΩ to 14MΩ, 1MΩ to 13MΩ, 1MΩ to 12MΩ, 1MΩ to 11MΩ, 1MΩ to 10MΩ, 2MΩ to 10MΩ or 3MΩ to 10MΩ. When this range is met, the electrostatic applicability is improved, thereby effectively producing yarns with nanometer-sized diameters. In addition, the biodegradable nonwoven fabric comprising the yarn is light in weight and has a high surface area and porosity, so it can also be applied to products that require moisture absorption.

[0338] More specifically, Figure 1 An apparatus for preparing a biodegradable resin composition according to an embodiment is schematically illustrated. Figure 1 The apparatus may include a slurry agitator 100 , an esterification reaction unit 200 , a polycondensation reaction unit 300 , a post-processing unit 400 , a first recovery unit 510 , and a second recovery unit 520 .

[0339] The step of preparing the biodegradable resin composition may include the step of preparing a slurry including a diol and an aromatic dicarboxylic acid.

[0340] This step may include a step of mixing and treating the diol and the aromatic dicarboxylic acid. That is, this step may be a pretreatment step before the esterification reaction and a step of mixing and slurrying the diol and the aromatic dicarboxylic acid. Here, the diol may include a biomass-based diol component.

[0341] The diol and the aromatic dicarboxylic acid may be fed into the slurry agitator 100 and agitated therein to produce slurry.

[0342] By mixing and pre-treating the diol and the aromatic dicarboxylic acid to form a slurry, the diol and the aromatic dicarboxylic acid can be uniformly reacted. The mixing and pre-treating of the diol and the aromatic dicarboxylic acid also effectively accelerates the esterification reaction, thereby improving the reaction efficiency.

[0343] In particular, when aromatic dicarboxylic acids (such as terephthalic acid) have complete crystallinity and are in powder form, their solubility in glycol is extremely low, making it difficult for homogeneous reaction to occur. Therefore, the pretreatment process of forming a slurry plays an important role in achieving the excellent physical properties of the biodegradable nonwoven fabric according to the present invention.

[0344] When the aromatic dicarboxylic acid is terephthalic acid, terephthalic acid has perfect crystallinity and is white crystals, which sublime at about 300° C. under normal pressure and have no melting point, so its solubility in diol is extremely low, making it difficult to undergo a homogeneous reaction.

[0345] When the aromatic dicarboxylic acid is terephthalic acid, terephthalic acid has perfect crystallinity and is white crystals, which sublime at about 300°C under normal pressure and have no melting point, so its solubility in diols is extremely low, making it difficult to undergo a homogeneous reaction. Therefore, when a pretreatment process is performed before esterification, a uniform reaction can be induced by increasing the surface area for reaction with diols in a solid matrix of terephthalic acid.

[0346] Furthermore, when the aromatic dicarboxylic acid is dimethyl terephthalic acid, the dimethyl terephthalic acid may be made into a molten state at about 142° C. to 170° C. through a pretreatment process and reacted with the diol, so that esterification may be performed faster and more efficiently.

[0347] In the pretreatment step of preparing the slurry, the structure and properties of the biodegradable resin composition may vary according to the particle size of the aromatic dicarboxylic acid, the particle size distribution, the pretreatment reaction conditions, and the like.

[0348] For example, aromatic dicarboxylic acids can include terephthalic acid. In particle size distribution (PSD), the average particle diameter (D50) of terephthalic acid can be 10 μm to 400 μm, measured by particle size analyzer Microtrac S3500, and can have a standard deviation of 100 or less for the average particle diameter (D50). Standard deviation means the square root of variance. The average particle diameter (D50) of terephthalic acid can be 20 μm to 200 μm, 30 μm to 180 μm, or 50 μm to 150 μm. When the average particle diameter (D50) of terephthalic acid meets these ranges, it may be more advantageous in improving solubility and reaction rate in diols.

[0349] During the pretreatment process, the diol and the aromatic dicarboxylic acid may be mixed and fed into a slurry agitator (tank) 100 .

[0350] For example, the slurry agitator 100 may have an anchor-type bottom and a height of 20 mm or more from the agitator. In addition, the slurry agitator 100 may be equipped with 2 or more rotating blades, which may be more advantageous in achieving an effective agitation effect.

[0351] For example, the height from the slurry agitator 100 may be 20 mm or higher, that is, the supply line and the bottom of the agitator may be almost connected to each other. In this case, slurry can be obtained without precipitation. If the shape, form and spinning blades of the agitator do not meet the above conditions, when the diol and the aromatic dicarboxylic acid are initially mixed, the aromatic dicarboxylic acid may be deposited to the bottom. In this case, phase separation may occur.

[0352] The pretreatment process of preparing the slurry may include the steps of mixing the diol and the aromatic dicarboxylic acid and stirring at about 30° C. to about 100° C. at about 50 rpm to about 200 rpm for 10 minutes or more, or 10 minutes to 200 minutes.

[0353] The diols may have the characteristics described above.

[0354] The diol may be added all at once or in divided doses. For example, the diol may be added separately when mixed with the aromatic dicarboxylic acid and after mixed with the aliphatic dicarboxylic acid.

[0355] The aromatic dicarboxylic acid may have the above-mentioned characteristics.

[0356] In the pretreatment step of preparing the slurry, the molar ratio of the diol to the aromatic dicarboxylic acid may be about 0.8:1 to about 1.2:1. In the pretreatment step of preparing the slurry, the molar ratio of the diol to the aromatic dicarboxylic acid may be about 0.9:1 to about 1.1:1.

[0357] When the added amount of the diol is larger than that of the aromatic dicarboxylic acid, the aromatic dicarboxylic acid can be easily dispersed.

[0358] Furthermore, additives may be added to the slurry. At least one of nanocellulose and a metal salt may be added to the slurry.

[0359] The step of preparing the biodegradable resin may include the step of esterifying the syrup and an aliphatic dicarboxylic acid to prepare a prepolymer.

[0360] The slurry and the aliphatic dicarboxylic acid may react in the esterification reaction unit 200 .

[0361] In esterification, the reaction time can be shortened by using the slurry. For example, the slurry obtained from the pretreatment step can shorten the esterification reaction time by 1.5 times or more.

[0362] The esterification may be performed at least twice. The prepolymer to be added to the condensation polymerization process may be formed by esterification.

[0363] For example, esterification can be performed immediately after adding aliphatic dicarboxylic acid or diol and aliphatic dicarboxylic acid to the slurry. That is, esterification can be performed when the slurry is fed into the esterification reactor, and only aliphatic dicarboxylic acid or aliphatic dicarboxylic acid and diol are fed into the esterification reactor.

[0364] The esterification may be performed at about 250° C. or less for about 0.5 hour to about 5 hours. In particular, the esterification may be performed at about 180° C. to about 250° C., about 185° C. to about 240° C., or about 200° C. to about 240° C. under normal pressure or reduced pressure until the theoretical amount of water as a byproduct reaches 95%. For example, the esterification may be performed for 0.5 hour to 5.5 hours, 0.5 hour to 4.5 hours, or 1 hour to 4 hours, but the present invention is not limited thereto.

[0365] For example, the slurry may be mixed with at least one of polycarbonate diol and polyether polyol to perform a first esterification reaction. Alternatively, the polycarbonate diol and polyether polyol may be introduced into a second esterification.

[0366] After the first esterification, the mixture of aliphatic dicarboxylic acid and diol may be fed into the esterification reaction part 200, and the second esterification may be performed with the first esterification product. At least one of polycarbonate diol and polyether polyol may be added to the second esterification reaction.

[0367] The first esterification reaction may be performed at a temperature of 250° C. or lower for 1.25 to 4 hours. For example, the first esterification reaction may be performed at normal pressure or reduced pressure until water as a by-product theoretically reaches 95% at 180° C. to 250° C., 185° C. to 240° C., or 200° C. to 240° C. For example, the first esterification reaction may be performed for 1.25 to 4 hours, 1.25 to 3.5 hours, or 2.5 to 3 hours, but the present invention is not limited thereto.

[0368] The second esterification reaction may be performed at a temperature of about 250° C. or less for 0.25 to 3.5 hours. For example, the second esterification reaction may be performed at normal pressure or reduced pressure until water as a byproduct theoretically reaches 95% at 180° C. to 250° C., 185° C. to 240° C., or 200° C. to 240° C. For example, the second esterification reaction may be performed for 0.5 to 3 hours, 1 to 2.5 hours, or 1.5 to 2.5 hours, but embodiments of the present invention are not limited thereto.

[0369] In the first and second esterifications, the ratio of the number of the first block to the second block, etc. can be controlled by adjusting the reaction temperature, reaction time, and the content of the diol, aromatic dicarboxylic acid, and aliphatic dicarboxylic acid added, respectively. In addition, when the esterification is divided into the first esterification and the second esterification, the total esterification can be accurately controlled. Therefore, when the esterification is performed in a partitioned manner, the reaction stability and reaction uniformity of the esterification can be improved.

[0370] In addition, in the second esterification, a branching agent may be additionally added. That is, a prepolymer may be formed by reacting a mixture of aliphatic dicarboxylic acid and diol, a branching agent, and the first esterification product. The characteristics and content of the branching agent may be the same as described above.

[0371] By esterification reaction, a prepolymer can be formed.

[0372] The number average molecular weight of the prepolymer can be about 500 g / mol to about 10,000 g / mol. For example, the number average molecular weight of the prepolymer can be about 500 g / mol to about 8,500 g / mol, about 500 g / mol to about 8,000 g / mol, about 500 g / mol to about 7,000 g / mol, about 500 g / mol to about 5,000 g / mol, or about 800 g / mol to about 3,000 g / mol. When the number average molecular weight of the prepolymer meets this range, the molecular weight of the polymer can be effectively increased in the polycondensation reaction.

[0373] The number average molecular weight can be measured using gel permeation chromatography (GPC). In particular, data generated by gel permeation chromatography includes several items such as Mn, Mw, and Mp, but the molecular weight can be measured based on the number average molecular weight (Mn).

[0374] Reinforcement material, branching agent, polycarbonate diol, polyether polyol, metal salt etc. can be added with slurry before esterification. Reinforcement material, branching agent, polycarbonate diol, polyether polyol, metal salt etc. can be fed into esterification section 200 in the middle of esterification. Reinforcement material, branching agent, polycarbonate diol, polyether polyol, metal salt etc. can be added into esterification product after esterification. Reinforcement material, branching agent, polycarbonate diol, polyether polyol, metal salt etc. can be added with aliphatic dicarboxylic acid before esterification. Reinforcement material, branching agent, polycarbonate diol, polyether polyol, metal salt etc. can be fed into esterification section 200 after the first esterification and before the second esterification.

[0375] Since the reinforcing material and the metal salt are fed into the esterification reaction, the reinforcing material and the metal salt may be uniformly dispersed in the biodegradable resin.

[0376] The reinforcing material may have the above characteristics. In particular, nanocellulose may be used as a reinforcing material.

[0377] Nanocellulose can be pre-treated by a bead mill or ultrasound before adding. Specifically, the nanocellulose can be water-dispersed nanocellulose pre-treated with a bead mill or pre-treated with ultrasound.

[0378] A vertical mill or a horizontal mill can be used as a wet milling device for bead mill pretreatment. A horizontal mill is preferred because the amount of beads that can be filled into the chamber is larger, and uneven wear of the machine is reduced, wear of the beads is reduced, and maintenance is easier, but the present invention is not limited thereto.

[0379] Bead mill pretreatment may be performed using one or more bead types selected from the group consisting of zirconium, zircon, zirconia, quartz, and alumina.

[0380] In particular, beads having a diameter of about 0.3 mm to about 1 mm can be used for bead mill pretreatment. For example, the diameter of the beads can be about 0.3 mm to about 0.9 mm, about 0.4 mm to about 0.8 mm, about 0.45 mm to about 0.7 mm, or about 0.45 mm to about 0.6 mm.

[0381] When the diameter of the beads satisfies the range, the dispersibility of the nanocellulose can be further improved. When the diameter of the beads exceeds the range, the average particle size and average particle deviation of the nanocellulose increase, resulting in low dispersibility.

[0382] In addition, in the bead mill pretreatment, it is preferred to use beads with a specific gravity higher than that of nanocellulose because sufficient energy can be delivered. For example, the beads can be one or more selected from the group consisting of zirconium, zircon, zirconium oxide, quartz and alumina, which have a higher specific gravity than water-dispersible nanocellulose, and zirconium beads having a specific gravity four times or more than that of water-dispersible nanocellulose are preferred, but are not limited thereto.

[0383] In addition, the ultrasonic pretreatment is a method of physically closing or crushing nanoparticles using waves generated by emitting 20 kHz ultrasound into a solution.

[0384] Ultrasonic pretreatment can be carried out less than 30 minutes under 30000J / s or less output.For example, ultrasonic pretreatment can be carried out 25 minutes or less time, 20 minutes or less time or 18 minutes or less time under 25000J / s or less or 22000J / s or less output.When output and execution time meet above-mentioned scope, the effect of ultrasonic pretreatment can be maximized, i.e. the improvement of dispersibility.When output exceeds above-mentioned scope, nanoparticles may be considerably reassembled and dispersibility may reduce.

[0385] Nanocellulose can be pretreated with a bead mill or with ultrasound. Alternatively, nanocellulose can be pretreated with a bead mill and with ultrasound. Here, in terms of improving dispersibility by preventing reaggregation, it is preferred to perform ultrasound pretreatment after pretreatment with a bead mill.

[0386] Since nanocellulose includes ionically bonded metals, its dispersibility in water can be very high. In addition, by bead mill pretreatment and ultrasonic pretreatment, an aqueous dispersion of nanocellulose with extremely high dispersibility can be obtained. The content of nanocellulose in the nanocellulose aqueous dispersion can be about 1% by weight to about 50% by weight.

[0387] In the esterification reaction, a titanium-based catalyst and / or a germanium-based catalyst may be used. In particular, a titanium-based catalyst and / or a germanium-based catalyst may be added to the slurry, and the esterification reaction may be performed.

[0388] Furthermore, before the first esterification reaction, a titanium-based catalyst and / or a germanium-based catalyst may be added to the slurry, and the titanium-based catalyst and / or the germanium-based catalyst may be further added to the product of the first esterification reaction.

[0389] The biodegradable resin may include one or more germanium-based catalysts selected from the group consisting of isopropoxytitanium, antimony trioxide, dibutyltin oxide, tetrapropyl titanate, tetrabutyl titanate, tetraisopropyl titanate, antimony acetate, calcium acetate and magnesium acetate, or selected from the group consisting of germanium oxide, germanium methanol, germanium ethanol, tetramethyl germanium, tetraethyl germanium and germanium sulfide.

[0390] In addition, based on the total weight of the diol, the aromatic dicarboxylic acid and the aliphatic dicarboxylic acid, the content of the catalyst can be about 100 ppm to 2000 ppm. For example, the content of the titanium-based catalyst or the germanium-based catalyst included can be about 100 ppm to about 1,600 ppm, about 150 ppm to about 1,400 ppm, about 200 ppm to about 1,200 ppm, or about 250 ppm to about 1,100 ppm. When the content of the catalyst meets the range, the performance can be further improved.

[0391] In addition, the heat stabilizer can be added with the slurry before esterification. The heat stabilizer can be fed into the esterification unit 200 in the middle of the esterification. The heat stabilizer can be added to the esterification product after esterification. In addition, the heat stabilizer can be added with the aliphatic dicarboxylic acid. In addition, the heat stabilizer can be fed into the esterification unit 200 after the first esterification and before the second esterification.

[0392] The thermal stabilizer may be characterized as described above.

[0393] Based on the total weight of glycol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, the content of heat stabilizer can be 3,000ppm or less. In particular, based on the total weight of glycol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid, the content of heat stabilizer can be 10ppm to 3,000ppm, 20ppm to 2,000ppm, 20ppm to 1,500ppm or 20ppm to 1,000ppm. When the content of heat stabilizer meets the range, the polymer degradation caused by high temperature during the reaction process can be controlled, so the terminal groups of the polymer can be reduced and the color can be improved.

[0394] After the esterification is completed, one or more selected from the group consisting of additives (such as silicon dioxide, potassium or magnesium) and color correction agents (such as cobalt acetate) may be further added to the esterification product. That is, after the esterification is completed, the additives and / or color correction agents may be added and stabilized, and then the polycondensation reaction may be performed. The additives and / or color correction agents may be added after the esterification reaction is completed, and may be fed to the polycondensation reaction part 300 together with the prepolymer. Therefore, the additives and / or color correction agents may be uniformly dispersed in the biodegradable resin.

[0395] After the esterification reaction is completed, the inorganic filler can be added to the esterification reaction product. That is, after the esterification reaction is completed, the polycondensation reaction can be carried out after adding and stabilizing the inorganic filler. The characteristics of the inorganic filler are the same as above. The inorganic filler can be fed to the polycondensation reaction part 300 together with the prepolymer, and the polycondensation process can be carried out. Therefore, the inorganic filler can be uniformly dispersed in the biodegradable resin.

[0396] In addition, the first recovery part 510 may recover byproducts such as water from the esterification reaction part 200. The first recovery part 510 may recover byproducts generated by esterification by applying vacuum pressure to the esterification reaction part 200 or performing reflux.

[0397] The step of preparing the biodegradable resin may include the step of performing a polycondensation reaction of the prepolymer. The operation of performing the polycondensation reaction may be performed as follows.

[0398] The prepolymer may be fed into the polycondensation reaction part 300. In addition, at least one of a reinforcing material, a heat stabilizer, a color corrector, an inorganic filler, a metal salt, and other additives may be fed into the polycondensation reaction part 300 together with the prepolymer.

[0399] Next, the polycondensation reaction may be carried out at about 180° C. to about 280° C. and about 10 Torr or less for about 1 hour to about 5 hours. For example, the polycondensation reaction may be carried out at about 190° C. to about 270° C., about 210° C. to about 260° C., or about 230° C. to about 255° C., at about 0.9 Torr or less, about 0.7 Torr or less, about 0.2 Torr to about 10 Torr, about 0.3 Torr to about 0.9 Torr, or about 0.2 Torr to about 0.6 Torr for about 1.5 hours to about 5 hours, about 2 hours to about 4.5 hours, or about 2 hours to about 4 hours.

[0400] The polycondensation reaction may include a first polycondensation and a second polycondensation.

[0401] For example, the first polycondensation can be carried out at about 260° C. or less, about 250° C. or less, about 215° C. to about 250° C., about 215° C. to about 245° C., or about 230° C. to about 245° C. at about 1 Torr to about 200 Torr, about 2 Torr to about 100 Torr, about 4 Torr to about 50 Torr, about 5 Torr to about 45 Torr, or about 8 Torr to about 32 Torr for about 0.5 hour to about 3.5 hours, about 0.5 hour to about 3.0 hours, or about 0.5 hour to about 2.8 hours.

[0402] In addition, the second polycondensation can be carried out at about 220° C. to about 265° C., about 230° C. to about 260° C., or about 235° C. to about 255° C. at about 1 Torr or less, about 0.8 Torr or less, about 0.6 Torr or less, about 0.1 Torr to about 1 Torr, about 0.2 Torr to about 0.8 Torr, or about 0.2 Torr to about 0.6 Torr for about 0.5 hour to about 4 hours, about 1 hour to about 3.5 hours, or about 1.5 hours to about 3.5 hours.

[0403] In addition, before the polycondensation reaction, a titanium-based catalyst or a germanium-based catalyst may be further added to the prepolymer. In addition, before the polycondensation reaction, one or more selected from the group consisting of: additives such as silicon dioxide, potassium or magnesium; amine-based stabilizers such as trimethyl phosphate, triphenyl phosphate, trimethylphosphine, phosphoric acid, phosphorous acid or tetraethylenepentamine; and polymerization catalysts such as antimony trioxide, antimony trioxide or tetrabutyl titanate may be further added to the prepolymer.

[0404] The number average molecular weight of the polymer can be about 40,000 g / mol or higher. For example, the number average molecular weight of the polymer can be about 43,000 g / mol or higher, about 45,000 g / mol or higher or about 50,000 g / mol to about 70,000 g / mol. When the number average molecular weight of the polymer meets this range, physical properties, impact resistance, durability and formability can be further improved.

[0405] In addition, the second recovery part 520 may recover byproducts such as water from the polycondensation reaction part 300. The second recovery part 520 may apply vacuum pressure to the polycondensation reaction part 300, and may recover byproducts generated in the polycondensation reaction.

[0406] The second recovery part 520 may apply a vacuum pressure of about 0.1 Torr to about 1 Torr to the inside of the polycondensation reaction part 300. The second recovery part 520 may apply a vacuum pressure of about 0.1 Torr to about 0.9 Torr to the inside of the polycondensation reaction part 300.

[0407] Next, the coating agent can be added to the polymer. In addition, the anti-hydrolysis agent and / or the chain extender can be added to the polymer. Next, the polymer and the coating agent can be uniformly mixed and maintained at about 200° C. to about 260° C. for about 1 minute to about 15 minutes. In addition, the polymer, the anti-hydrolysis agent and the chain extender can be uniformly mixed and maintained at about 200° C. to about 260° C. for about 1 minute to about 15 minutes. Therefore, the polymer can react with the coating agent. The polymer can react with the anti-hydrolysis agent and / or the chain extender.

[0408] The characteristics of the application agent and the chain extender are the same as described above.

[0409] The step of preparing the biodegradable resin may include the step of making pellets from the polymer.

[0410] Specifically, the polymer may be cooled to about 15° C. or less, about 10° C. or less, or about 6° C. or less, and the cooled polymer may then be cut to produce pellets.

[0411] The cutting step may be performed without limitation using any pellet cutting machine used in the art, and the pellets may have various shapes. As a pellet cutting method, an underwater cutting method or a strand cutting method may be used.

[0412] The pellets may undergo additional post-processing processes. The pellets may be fed to a post-processing section 400 and may undergo a post-processing process.

[0413] The post-processing process may be performed in the post-processing part 400. The pellets may be fed into the post-processing part 400. Next, the post-processing part 400 may melt and re-extrude the fed pellets by friction heat. That is, the post-processing part 400 may include an extruder such as a twin-screw extruder.

[0414] The temperature of the post-treatment process may be about 230°C to about 270°C. The temperature of the post-treatment process may be about 230°C to about 260°C. The temperature of the post-treatment process may be about 240°C to about 265°C. The temperature of the post-treatment process may be about 240°C to about 260°C.

[0415] The post-treatment process time can be about 30 seconds to about 3 minutes. The post-treatment process time can be about 50 seconds to about 2 minutes. The post-treatment process time can be about 1 minute to about 2 minutes.

[0416] Next, the resin extruded by the extruder can be cooled, cut and processed into pellets for post-treatment. That is, the resin extruded by the extruder can be reprocessed into pellets through the above-mentioned cutting step.

[0417] During the post-treatment process, the crystallinity of the pellets can be improved. In addition, the content of the residue included in the pellets can be adjusted during the post-treatment process. Specifically, the content of the oligomers included in the pellets can be controlled by the post-treatment process. The amount of the residual solvent contained in the pellets can be controlled by the post-treatment process.

[0418] Therefore, the post-treatment process can appropriately control the mechanical properties, biodegradability, UV resistance, optical characteristics or hydrolysis resistance of the biodegradable polyester resin.

[0419] After the pellets are produced, the biodegradable resin may be mixed with the heterogeneous biodegradable resin. In addition, at least one of an application agent, an inorganic filler, a light stabilizer, a color correction agent, and other additives may be mixed with the biodegradable resin and the heterogeneous biodegradable resin.

[0420] The mixing process can be as follows.

[0421] Biodegradable resin and heterogeneous biodegradable resin are mixed with at least one of an application agent, an inorganic filler, a heat stabilizer, a color correction agent, a metal salt or other additives, and fed into an extruder. The mixed biodegradable resin composition is melted and mixed in an extruder at about 180°C to about 260°C. Next, the melt-mixed biodegradable resin composition can be extruded, cooled, cut and re-granulated. By this method, the biodegradable polyester resin composition according to the present invention can be prepared by combining it with a heterogeneous biodegradable resin.

[0422] Alternatively, the application agent, inorganic filler, heat stabilizer, color correction agent, metal salt and other additives may be added during the process of polymerizing the biodegradable resin.

[0423] The biodegradable resin solution may include a biodegradable resin composition produced in various steps and an organic solvent. The biodegradable resin composition may be mixed with the organic solvent.

[0424] To produce a biodegradable nonwoven fabric, the biodegradable resin composition can be dissolved with an organic solvent during the electrospinning process. The biodegradable resin composition can be dissolved in an organic solvent to produce a biodegradable resin solution.

[0425] The organic solvent may include a mixture of two or more solvents. There is no particular limitation on the type of the organic solvent, but may include at least one of dichloromethane (DCM) and dimethylformamide (DMF).

[0426] The organic solvent may include a mixture of DCM and DMF. The organic solvent may be a mixture of DCM and DMF mixed in a volume ratio of 1:10 to 10:1, 2:9 to 9:2, 3:8 to 8:3 or 4:7 to 7:4. The solid content in the biodegradable resin solution may be 10% to 50% by weight, 10% to 40% by weight, 10% to 30% by weight, 10% to 20% by weight or 10% to 18% by weight. When this range is met, the biodegradable resin solution may have an appropriate surface tension, thereby inhibiting the formation of beads in the biodegradable nonwoven fabric.

[0427] The biodegradable resin solution may have a weight average molecular weight (Mw) of 50,000 g / mol to 200,000 g / mol, 50,000 g / mol to 180,000 g / mol, 50,000 g / mol to 150,000 g / mol, or 60,000 g / mol to 120,000 g / mol.

[0428] The viscosity of the biodegradable resin solution may be 10 cP to 500 cP, 10 cP to 480 cP, 10 cP to 450 cP, 10 cP to 430 cP, or 10 cP to 400 cP.

[0429] When the molecular weight and viscosity ranges are met, the discharge amount can be uniform and continuous fibers can be formed.

[0430] The surface tension of the biodegradable resin solution can be 10mM / m -1 Up to 50mM / m -1 、10mM / m -1 To 45mM / m -1 、10mM / m -1 Up to 40mM / m -1 or 20mM / m -1 Up to 40mM / m -1 When this range is satisfied, a uniform nano-sized fiber phase can be formed. In addition, the nano-sized fiber phase can be continuously formed.

[0431] The method for manufacturing a biodegradable nonwoven fabric according to the present invention includes the steps of preparing a biodegradable resin solution including a biodegradable resin composition and an organic solvent, wherein the biodegradable resin composition includes a first biodegradable resin, and then applying a voltage to the biodegradable resin solution to spin the biodegradable resin solution.

[0432] Figure 2 Schematically shows an apparatus for manufacturing a biodegradable nonwoven fabric by electrospinning according to an embodiment. Figure 2 The device 10 may include a storage unit 1 for storing and moving a biodegradable resin solution and a nozzle unit 2. The storage unit 1 may include a pump, such as a syringe pump. The biodegradable resin solution may be moved to the nozzle unit 2 by the syringe pump.

[0433] Charges may be induced by a voltage generating device on the surface of the droplets of the biodegradable resin solution moving to the nozzle part 2. The charges generated on the surface of the biodegradable resin solution may generate a force opposing the surface tension of the biodegradable resin solution.

[0434] As the intensity of the electric field generated by the voltage generating device increases, the hemisphere of the biodegradable resin solution formed at the end of the nozzle portion 2 may be elongated.

[0435] The hemisphere may be formed into a cone shape in the form of a Taylor cone. When the charge repulsive force of the biodegradable resin solution overcomes the surface tension of the hemisphere of the biodegradable resin solution, the charged biodegradable resin solution may be spun from the end of the nozzle part 2 .

[0436] In the step of spinning a biodegradable resin solution, the voltage that can be applied to the biodegradable resin solution is 5kV to 50kV, 10kV to 50kV, 15kV to 50kV, 15kV to 40kV, 15kV to 35kV or 15kV to 30kV. When this range is met, a Taylor cone shape can be smoothly formed. In addition, a uniform nano-sized fiber phase can be formed, and the formation of beads in the biodegradable nonwoven fabric can be suppressed.

[0437] In the step of spinning the biodegradable resin solution, the discharge rate of the biodegradable resin solution may be 0.1 mL / min to 5.0 mL / min, 0.1 mL / min to 4.0 mL / min, 0.1 mL / min to 3.0 mL / min, 0.1 mL / min to 2.0 mL / min, or 0.1 mL / min to 1.0 mL / min. When this range is met, polarization of the biodegradable resin solution may occur smoothly, thereby suppressing the formation of powder and beads in the biodegradable nonwoven fabric.

[0438] The apparatus for spinning a biodegradable resin solution may include a first region 3 from which the biodegradable resin solution is discharged; and a second region 4, which is separated from the first region 3 and includes yarn made of the biodegradable resin solution discharged from the first region 3. The biodegradable resin solution may be discharged from the first region 3 as a charged jet, and the discharged jet may be connected to the previous jet by viscosity to form a continuous jet 5. In addition, when the jet 5 moves through the air in the direction of gravity, the jet 5 may be made into a yarn by evaporating the solvent contained in the biodegradable resin solution. The yarn may be randomly stacked in the second region 4 to form a biodegradable nonwoven fabric.

[0439] The distance A between the first region 3 and the second region 4 may be 50 mm to 1,000 mm, 50 mm to 900 mm, 100 mm to 900 mm, 100 mm to 800 mm, 100 mm to 700 mm, 100 mm to 600 mm, or 100 mm to 500 mm. When this range is satisfied, the solvent contained in the biodegradable resin solution may be sufficiently evaporated, so that nano-sized yarns may be produced, and the formation of beads in the biodegradable nonwoven fabric may be suppressed.

[0440] The method for manufacturing a biodegradable nonwoven fabric may further include spinning a biodegradable resin solution to produce a biodegradable nonwoven fabric, and then drying the biodegradable nonwoven fabric. Through the drying step, the solvent contained in the biodegradable resin solution can be evaporated more effectively, thereby manufacturing a biodegradable nonwoven fabric comprising nano-sized yarns with improved uniformity.

[0441] Drying can be carried out at 10°C to 40°C, 15°C to 40°C, 15°C to 35°C, 15°C to 30°C, preferably at room temperature. The drying time can be 10 minutes to 60 minutes, 10 minutes to 50 minutes, 10 minutes to 64 minutes, or 10 minutes to 30 minutes.

[0442] The biodegradable nonwoven fabric according to the present invention comprises: a first biodegradable resin comprising a diol, an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid; a biodegradable resin composition comprising the first biodegradable resin; and a yarn comprising the biodegradable resin composition and having a diameter of 50 nm to 1,000 nm, wherein the biodegradable resin composition has a resistance of 3 MΩ to 10 MΩ in a molten state.

[0443] The first biodegradable resin and the biodegradable resin composition may be the same as the first biodegradable resin and the biodegradable resin composition described above.

[0444] The biodegradable nonwoven fabric comprises yarns having a diameter of 1 nm to 1,000 nm, 5 nm to 1,000 nm, 10 nm to 1,000 nm, 20 nm to 1,000 nm, 30 nm to 1,000 nm, 40 nm to 1,000 nm, or 50 nm to 1,000 nm. The resistance of the biodegradable resin composition in a molten state may be 1 MΩ to 15 MΩ, 1 MΩ to 14 MΩ, 1 MΩ to 13 MΩ, 1 MΩ to 12 MΩ, 1 MΩ to 11 MΩ, 1 MΩ to 10 MΩ, 2 MΩ to 10 MΩ, or 3 MΩ to 10 MΩ. When these ranges are met, the biodegradable nonwoven fabric is lightweight and has a high surface area and porosity, so it can be applied to products requiring hygroscopicity.

[0445] Based on the gross weight of yarn, the content of the organic solvent included can be 100ppm or less, 90ppm or less, 80ppm or less, 50ppm or less, 30ppm or less, 10ppm or less or 0.1ppm to 10ppm.The organic solvent can be identical with above-mentioned organic solvent.When satisfying these scopes, yarn with uniform diameter can be produced, thereby the product reliability of the biodegradable nonwoven fabric produced by this yarn can be improved.

[0446] The yarn may include an applicator. The applicator may be an electrostatic applicator. The applicator may inhibit the formation of beads in the biodegradable nonwoven fabric.

[0447] There is no particular limitation on the type of the application agent, but it may be at least one of potassium acetate (CH3COOK) and magnesium acetate (Mg(CH3COO)).

[0448] Based on the total weight of the yarn, the content of the application agent can be 1ppm to 500ppm, 1ppm to 400ppm, 5ppm to 400ppm, 5ppm to 300ppm, 7ppm to 300ppm, 7ppm to 200ppm, 7ppm to 150ppm, 9ppm to 150ppm, 10ppm to 150ppm or 10ppm to 100ppm. When these ranges are met, the biodegradable nonwoven fabric is lightweight and has a high surface area and porosity, so it can be applied to products requiring hygroscopicity.

[0449] The biodegradable resin composition according to the present invention includes a biodegradable resin including a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid. The biodegradable resin composition has a resistance of 3MΩ to 10MΩ in a molten state.

[0450] The diol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid may be the same as the diol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid described above.

[0451] The biodegradable resin composition may include an application agent. The application agent may be the same as the application agent described above.

[0452] Hereinafter, the present invention will be described in more detail based on the following Examples and Comparative Examples. However, the Examples and Comparative Examples are provided only as examples to describe the present invention in more detail, and the present invention is not limited to the following Examples and Comparative Examples.

[0453] Preparation Example

[0454] Preparation of pretreated nanocellulose

[0455] Dry powder type cellulose nanocrystals (NVC-100, manufacturer: Celluforce) having a particle size of about 1 μm to about 50 μm were dispersed in water at 1% by weight, and then sonicated using a tip type ultrasonic disperser at an output of 20,000 J / s for 1 minute, thereby producing pretreated nanocellulose.

[0456] Preparation of PBAT resin

[0457] 1. Preparation of PBAT Resin #1

[0458] -First step: pretreatment to obtain slurry

[0459] In a catalyst-free state, nanocellulose pretreated according to the preparation example, metal salt, branching agent, ester polyol, 1,4-butanediol (1,4-BDO) and terephthalic acid (TPA) were mixed and fed into a slurry tank (the bottom of the slurry tank was anchor-shaped, the height from the stirrer was 40 mm, and three rotating blades were provided). Here, the molar ratio of 1,4-butanediol (1,4-BDO) to terephthalic acid (TPA) was 1.4:1, and the D of terephthalic acid (TPA) was 1.5:1. 50 The mixture fed into the slurry tank was stirred at 60° C. and 100 rpm for 1 hour to obtain a slurry without phase separation. The contents of the pretreated nanocellulose, metal salt, branching agent and ester polyol are shown in Table 1 below.

[0460] -Step 2: Obtaining prepolymer

[0461] The slurry obtained in the first step was fed into a reactor through a supply line, 250 ppm of a titanium-based catalyst tetrabutyl titanate (Dupont, manufactured by Tyzor TnBT) based on the total weight of the slurry was fed into the reactor, and then the first esterification was performed at 220° C. and normal pressure for about 1 hour and 30 minutes until 95% of by-product water was discharged.

[0462] To the first esterification reaction product, 53 mol% of 1,4-butanediol (1,4-BDO) based on the total moles of the diol component, 53 mol% of adipic acid (AA) based on the total moles of the dicarboxylic acid component, and 200 ppm of a titanium-based catalyst tetrabutyl titanate (Dupont, manufactured by Tyzor TnBT) based on the total molar weight of the diol and dicarboxylic acid components were added. Next, a second esterification reaction was performed at 220° C. and normal pressure for about 2 hours and 30 minutes until 95% of by-product water was discharged, thereby producing a prepolymer having a number average molecular weight of 5,500 g / mol.

[0463] -Step 3: Polycondensation reaction

[0464] Based on the total weight of the prepolymer obtained in the second step, 150ppm of titanium-based catalyst tetrabutyl titanate (Dupont, manufactured by Tyzor TnBT) and 500ppm of triethyl phosphate stabilizer were added, and then stabilized for about 10 minutes. Next, after raising the temperature to 240°C, a 2-hour polycondensation reaction was carried out at 0.5 Torr to produce a polymer with a number average molecular weight of 25,000g / mol. Next, the polymer was cooled to 5°C and cut with a pelletizer to obtain PBAT resin #1 pellets.

[0465] 2. Production of PBAT resin #2 to #5

[0466] PBAT resin #2 to #5 pellets were manufactured in the same process as the production process of PBAT resin #1, except that the components and contents shown in Table 1 below and the temperatures and times of the first and second esterification reactions and the temperature and time of the polycondensation reaction shown in Table 2 below were used.

[0467] Table 1

[0468]

[0469] Table 2

[0470]

[0471]

[0472] Preparation of biodegradable resin composition

[0473] 1. Preparation of Biodegradable Resin Composition #1

[0474] A raw material composition was prepared using the components and contents shown in the following Table 3. Next, the raw material composition was fed into a T-die extrusion molding device (20 mm, L / D=25, manufactured by Toyo Seiki Seisaku-sho, Ltd) equipped with a twin screw as an extrusion molding machine, and kneaded at 160° C. to produce a pelletized biodegradable resin composition #1.

[0475] 2. Preparation of Biodegradable Resin Compositions #2 to #9

[0476] Biodegradable resin composition #2 to #9 pellets were prepared in the same manner as the preparation method of biodegradable resin composition #1, except that the components and contents shown in Table 3 below were used.

[0477] Table 3

[0478]

[0479]

[0480] Example

[0481] Example 1

[0482] The biodegradable resin composition #1 was dissolved in an organic solvent in which dichloromethane (DCM) and dimethylformamide (DMF) were mixed in a volume ratio of 3:2, thereby preparing a biodegradable resin solution. The solid content in the biodegradable resin solution was 14% by weight. Next, the biodegradable resin solution was spun at a voltage of about 25 kV, a radiation distance of about 15 cm, and a solution release rate of about 0.5 ml / min under the conditions of a temperature of about 25° C. and a relative humidity of about 28%, thereby preparing a sheet-like biodegradable nonwoven fabric containing nano yarns having a thickness of about 0.5 mm.

[0483] Example 2

[0484] A biodegradable nonwoven fabric was prepared in the same manner as in Example 1, except that the nano yarn of Example 1 was dried at room temperature for 30 minutes, and then manufactured into a sheet-shaped biodegradable nonwoven fabric having a thickness of about 0.5 mm.

[0485] Examples 3 to 14 and Comparative Examples 1 to 4

[0486] A biodegradable nonwoven fabric was prepared in the same manner as in Example 1, except that the biodegradable resin composition, temperature, relative humidity, voltage, irradiation distance, and solution release rate shown in Table 4 below were used.

[0487] Table 4

[0488]

[0489]

[0490] Experimental example

[0491] Experimental Example 1 – Resistance in the Molten State

[0492] Each of the biodegradable resin compositions #1 to #9 was melted at about 240° C. under a nitrogen atmosphere, and then bubbles were removed. Next, a platinum electrode was inserted into each molten resin composition, and then the resistance in the molten state was measured at about 50 V for about 120 sec. The resistance in the molten state was calculated according to the following equation 10, and the results are summarized in the following Table 5:

[0493] Equation 10

[0494] Resistance in molten state (MΩ) = A / L × V / I

[0495] In Equation 10, A is the area of ​​the electrode (cm 2 ), L is the distance between the electrodes, I is the applied current, and V is the applied voltage.

[0496] Experimental Example 2 – Biodegradability

[0497] Each of the biodegradable resin compositions #1 to #9 was manufactured into a sheet having a thickness of 300 μm and a size of 30 mm×30 mm, and the initial number average molecular weight of the sheet was measured using the following gel permeation chromatography (GPC) instrument and measurement conditions.

[0498] Next, under the following composting conditions, the sheet was placed at a temperature of 60° C. and a humidity of 90% for 63 days, and then the number average molecular weight thereof was measured using the following gel permeation chromatography (GPC) instrument and measurement conditions. The value obtained by dividing the difference between the initial number average molecular weight and the number average molecular weight after 63 days by the initial number average molecular weight was taken as biodegradability. The results are shown in the following Table 5.

[0499] - Gel Permeation Chromatography (GPC) Instruments and Measurement Conditions

[0500] Sample pretreatment: 0.035 mg of the prepared flakes were dissolved in 1.5 ml of THF.

[0501] Measuring equipment: e2695 manufactured by Waters Corporation

[0502] Flow rate: 1 ml / min in THF

[0503] Flow rate: 50μl

[0504] Column temperature: 40°C

[0505] Detector: ELSD

[0506] Column: Styragel column HR 5E, HR4, HR2

[0507] - Composting conditions

[0508] Manufacturer: Taeheung F&G

[0509] Product name: Geosangto (1st level compost byproduct fertilizer)

[0510] Compost ingredients: 40% by weight of pig manure, 15% by weight of chicken manure, 37% by weight of sawdust, 5% by weight of zeolite, and 3% by weight of microbial agent.

[0511] Experimental Example 3 - Residual Solvent Content

[0512] The content of the residual solvent (DCM and DMF) in each of the biodegradable nonwoven fabric yarns manufactured in Examples 1 to 14 and Comparative Examples 1 to 4 was measured using TD-GCMS under the following instrument and measurement conditions:

[0513] -TD-GCMS instruments and conditions

[0514] TD: 8min, 320℃,

[0515] Capture purge time: 1min

[0516] Split ratio: 16

[0517] GC: Agilent 7890A

[0518] MS: Agilent 5975C

[0519] Column: DB-1

[0520] Flow rate: 1ml / min

[0521] Detector temperature: 300°C

[0522] Experimental Example 4 - Absorbency

[0523] Every kind of biodegradable nonwoven fabric prepared in embodiment 1 to 14 and comparative example 1 to 4 is made into the size of 100mm wide and 80mm long, and then the initial weight of nonwoven fabric is measured.Next, each nonwoven fabric is immersed in the saline solution for 20 seconds, and then its weight is measured.In addition, calculate the weight of nonwoven fabric after immersion relative to the ratio of the initial weight of nonwoven fabric.The results are shown in the following table 5.

[0524] Experimental Example 5 - Processability

[0525] Whether each of the biodegradable nonwoven fabrics manufactured in Examples 1 to 14 and Comparative Examples 1 to 4 maintained its shape was evaluated based on the following criteria, and the results are shown in Table 5 below.

[0526] -○: The nonwoven fabric shape is maintained.

[0527] - ×: The nonwoven fabric shape was not maintained.

[0528] Experimental Example 6 – Yarn Diameter and Shape

[0529] The diameter and shape of each biodegradable nonwoven fabric yarn produced in Examples 1 to 14 and Comparative Examples 1 to 4 were measured using a scanning electron microscope (SEM). The shape of the yarn was evaluated according to the following criteria, and the results are shown in Table 5 below.

[0530] -◎: Continuous fiber

[0531] -○: Continuous fibers, some beads present

[0532] -△: Beads and fibers mixed

[0533] -×: Micron-shaped ribbons formed

[0534] Table 5

[0535]

[0536]

[0537]

[0538] As shown in Tables 4 and 5, it was confirmed that the biodegradable nonwoven fabrics of Examples 1 to 14 prepared by applying a voltage to a solution prepared by mixing a biodegradable resin composition including a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid with an organic solvent showed excellent biodegradability and yarn quality, and were thus suitable for products requiring high absorbency.

[0539] More specifically, Figure 3A photograph of the biodegradable nonwoven fabric produced in Example 1 is shown, Figure 4 Shown is a photograph of the biodegradable nonwoven fabric produced in Comparative Example 1. It was confirmed that the biodegradable nonwoven fabric of Comparative Example 1 had a large amount of beads compared to Example 1, making it unsuitable for use as a nonwoven fabric.

[0540] Description of Reference Numerals

[0541] 1: Storage

[0542] 2: Nozzle

[0543] 3: First Area

[0544] 4: Second Area

[0545] 5: Jet

[0546] 10: Equipment

[0547] 100: Slurry agitator

[0548] 200: Esterification reaction section

[0549] 300: Polycondensation reaction section

[0550] 400: Post-processing unit

[0551] 510: First Recovery Department

[0552] 520: The second recovery department.

Claims

1. A method for producing a biodegradable nonwoven fabric, the method comprising: preparing a biodegradable resin solution including an organic solvent and a biodegradable resin composition including a first biodegradable resin; and spinning the biodegradable resin solution by applying a voltage to the biodegradable resin solution, Wherein, the first biodegradable resin comprises diol, aromatic dicarboxylic acid and aliphatic dicarboxylic acid.

2. The method according to claim 1, wherein: In the spinning step, the voltage applied to the biodegradable resin solution is 15 kV to 30 kV.

3. The method according to claim 1, wherein: In the spinning, a first area for discharging the biodegradable resin solution and a second area which is separated from the first area in the gravity direction and includes yarn produced from the biodegradable resin solution discharged from the first area are used, and The distance between the first area and the second area is 100 mm to 500 mm.

4. The method according to claim 1, wherein: The biodegradable resin composition further comprises a second biodegradable resin, and The second biodegradable resin comprises one or more selected from the group consisting of polybutylene succinate, polylactic acid, polybutylene adipate, polybutylene succinate-adipate, polybutylene succinate-terephthalate, polyhydroxybutyrate-valerate, polycaprolactone and polybutylene succinate-adipate-terephthalate.

5. The method according to claim 1, wherein: The biodegradable resin composition includes an application agent, and The application agent includes an amount of about 10 ppm to about 100 ppm based on the total weight of the biodegradable resin composition.

6. The method according to claim 1, wherein: The biodegradable resin composition in a molten state has an electrical resistance of 3 MΩ to 10 MΩ.

7. A biodegradable nonwoven fabric comprising: A first biodegradable resin includes a diol, an aromatic dicarboxylic acid, and an aliphatic dicarboxylic acid; A biodegradable resin composition, comprising the first biodegradable resin; as well as Yarn comprising the biodegradable resin composition and having a diameter of 50 nm to 1,000 nm, The resistance of the biodegradable resin composition in a molten state is 3 MΩ to 10 MΩ.

8. The biodegradable nonwoven fabric according to claim 7, wherein: The yarn includes an application agent.

9. A biodegradable resin composition comprising a biodegradable resin, wherein the biodegradable resin comprises a diol, an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid, The resistance of the biodegradable resin composition in a molten state is 3 MΩ to 10 MΩ.

10. The biodegradable resin composition according to claim 9, wherein The biodegradable resin composition includes an application agent.

Citation Information

Patent Citations

  • Preparation of polylactic acid and copolymers of lactic acids

    US4797468A

  • Production of high molecular weight polylactic acid

    US5470944A

  • Method for producing polylactic acid

    US5770682A

  • Process for preparing polylactic acid

    US5821327A

  • Method for producing polylactic acid and apparatus used therefor

    US5880254A